Adhesive composition, adhesive layer, adhesive sheet, optical member having adhesive layer, picture display unit and touch panel

The adhesive composition addresses unstable adhesive strength in image display devices and touch panels by controlling water absorption rates and times, ensuring stable performance and high reliability under varying environments.

JP2024179974APending Publication Date: 2024-12-26NITTO DENKO CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023099355
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-16
Publication Date
2024-12-26

AI Technical Summary

Technical Problem

Existing adhesive compositions for image display devices and touch panels, particularly in automotive applications, face challenges with unstable adhesive strength due to environmental changes, leading to reduced productivity and reliability issues.

Method used

An adhesive composition with specific water absorption rates and absorption time criteria (X90, X25, T90, T25) to stabilize adhesive strength, ensuring minimal change under varying environmental conditions, thereby enhancing productivity and reliability.

Benefits of technology

The adhesive composition provides stable adhesive strength and high reliability, allowing for efficient manufacturing of image display devices and touch panels that maintain performance under harsh environmental conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024179974000007
    Figure 2024179974000007
  • Figure 2024179974000008
    Figure 2024179974000008
  • Figure 2024179974000009
    Figure 2024179974000009
Patent Text Reader

Abstract

To provide an adhesive composition for forming an adhesive layer to be used to adhere an optical member of a picture display unit, the adhesive composition having high reliability with adhesive force thereof unlikely to change by an environmental change and a less change in the adhesive force by a storage environment immediately after a film production while capable of forming an adhesive layer excellent in productivity, and also to provide an adhesive layer, an adhesive sheet, an optical member having an adhesive layer, a picture display unit and a touch panel.SOLUTION: An adhesive composition is for forming an adhesive layer to be used to adhere an optical member of a picture display unit. A water absorption percentage X90(%) when the adhesive layer is stored for 360 minutes under a condition of 23°C and 90%RH satisfies an expression (1): X90≤1.5% (1).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive composition, a pressure-sensitive adhesive layer, a pressure-sensitive adhesive sheet, an optical member with a pressure-sensitive adhesive layer, an image display device, and a touch panel. [Background technology]

[0002] In recent years, image display devices such as liquid crystal displays (LCDs) and organic electroluminescence displays (OLEDs), as well as touch panels incorporating touch sensors in these image display devices, have been widely used in various fields. Such image display devices and touch panels have a configuration in which various optical members such as a polarizing film, a retardation film, an optical compensation film, a touch sensor film, and a cover film are laminated on an image display panel. Adhesive sheets having an adhesive layer are used to bond these optical members. For example, transparent adhesive sheets are used to bond various optical members in image display devices (see, for example, Patent Documents 1 to 3). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2003-238915 A [Patent Document 2] JP 2003-342542 A [Patent Document 3] JP 2004-231723 A Summary of the Invention [Problem to be solved by the invention]

[0004] The image display devices and touch panels are also widely used in in-vehicle displays such as car navigation devices. In-vehicle displays are often exposed to harsh environments such as high temperature, high humidity, and sunlight for long periods of time, and therefore require high reliability. In particular, with the spread of electric vehicles (EVs), screens are expected to become larger and more flexible in the future, and the required reliability is increasing year by year, so there is a demand for highly reliable adhesives whose properties such as adhesive strength are stable even when the environment changes. In addition, if the adhesive strength changes significantly depending on the storage environment immediately after the adhesive layer is formed, it is necessary to store the adhesive until the adhesive strength stabilizes, which causes a problem of reduced productivity.

[0005] Therefore, an object of the present invention is to provide an adhesive composition for forming an adhesive layer used for adhering optical components of an image display device, which adhesive composition has stable and highly reliable adhesive strength even when the environment changes, exhibits little change in adhesive strength depending on the storage environment immediately after film formation, and is capable of forming an adhesive layer with excellent productivity. Another object of the present invention is to provide a pressure-sensitive adhesive layer which has stable adhesive strength and high reliability even when the environment changes, which shows little change in adhesive strength depending on the storage environment immediately after film formation, and which has excellent productivity. Another object of the present invention is to provide an adhesive sheet having an adhesive layer which has high reliability with stable adhesive strength even when the environment changes, which shows little change in adhesive strength depending on the storage environment immediately after film formation, and which has excellent productivity. Another object of the present invention is to provide an optical component with a pressure-sensitive adhesive layer, which has a pressure-sensitive adhesive layer that has stable and highly reliable adhesive strength even when the environment changes, exhibits little change in adhesive strength depending on the storage environment immediately after film formation, and has excellent productivity. Another object of the present invention is to provide an image display device and a touch panel which include the pressure-sensitive adhesive layer-attached optical member and which are highly reliable even under changing environments, have excellent durability, and have high performance. [Means for solving the problem]

[0006] A first aspect of the present invention provides a pressure-sensitive adhesive composition for forming a pressure-sensitive adhesive layer used for attaching an optical member of an image display device. In this specification, the pressure-sensitive adhesive composition of the first aspect of the present invention may be referred to as the "pressure-sensitive adhesive composition of the present invention."

[0007] The pressure-sensitive adhesive composition of the present invention is used for forming a pressure-sensitive adhesive layer used for adhering optical members such as polarizing films, retardation films, optical compensation films, touch sensor films, and cover films to image display panels or for adhering these optical members to each other in image display devices such as liquid crystal displays (LCDs) and organic light-emitting diode displays (OLEDs) and touch panels in which a touch sensor is incorporated into these image display devices.

[0008] The adhesive composition of the present invention is particularly suitable for use in vehicle-mounted image display devices and touch panels. Vehicle-mounted displays are often exposed to harsh environments such as high temperature, high humidity, and sunlight for long periods of time, and are required to have high reliability such that properties such as adhesive strength are unlikely to change even when the environment changes. In addition, if the adhesive strength changes significantly depending on the storage environment immediately after the adhesive layer is formed, it is necessary to store the adhesive layer until the adhesive strength stabilizes, which causes a problem of reduced productivity.

[0009] In the pressure-sensitive adhesive composition of the present invention, when the pressure-sensitive adhesive layer is stored for 360 minutes under conditions of 23° C. and 90% RH, the water absorption rate X90(%) satisfies the following formula (1). X90≦1.5% (1)

[0010] The water absorption rate X90 is the proportion of water absorbed by the pressure-sensitive adhesive layer in a high humidity environment of 90% RH, and satisfies the above formula (1), i.e., the water absorption rate X90 is 1.5% or less. If the water absorption rate X90 is high, the swelling and shrinkage of the pressure-sensitive adhesive layer due to environmental changes will increase, causing a change in elastic modulus. In addition, the moisture contained in the pressure-sensitive adhesive will interact with the polar groups on the pressure-sensitive adhesive surface, inhibiting the interaction between the polar groups on the pressure-sensitive adhesive surface and the polar groups on the adherend surface, which may affect the adhesive strength. The configuration in which the water absorption rate X90 satisfies the above formula (1) is preferable in that a highly reliable pressure-sensitive adhesive layer whose adhesive strength is unlikely to change due to environmental changes such as temperature and humidity can be obtained. In addition, it is also preferable in that a pressure-sensitive adhesive layer whose adhesive strength changes little due to storage environment immediately after film formation and which has excellent productivity can be obtained.

[0011] In the pressure-sensitive adhesive composition of the present invention, when the water absorption rate when the pressure-sensitive adhesive layer is stored for 240 minutes under conditions of 23° C. and 25% RH is defined as X25 (%), it is preferable that the following formula (2) is satisfied. X90-X25≦1.5% (2)

[0012] The water absorption rate X25 is the proportion of water absorbed by the pressure-sensitive adhesive layer in a dry environment of 25% RH. As described above, the difference between the water absorption rate X90 and the water absorption rate X25 (X90-X25) satisfies the above formula (2), i.e., is preferably 1.5% or less. If the difference between the X25 and X90 is large, the amount of water contained in the pressure-sensitive adhesive layer changes greatly depending on the environment, and the influence on the adhesive strength also increases, and reliability may decrease. The configuration in which the difference X90-X25 satisfies the above formula (2) is preferable in that it provides a highly reliable pressure-sensitive adhesive layer that is unlikely to change in adhesive strength due to environmental changes such as temperature and humidity, and can be used in various environments. It is also preferable in that it provides a pressure-sensitive adhesive layer that has little change in adhesive strength due to storage environment immediately after film formation, and has excellent productivity.

[0013] In the pressure-sensitive adhesive composition of the present invention, when the time required for the pressure-sensitive adhesive layer to reach half of the water absorption rate X90(%) when stored for 360 minutes under conditions of 23°C and 75% RH from the water absorption rate X75(%) when stored for 360 minutes under conditions of 23°C and 90% RH is defined as T90 (min), it is preferable that the pressure-sensitive adhesive composition satisfies the following formula (3): T90≧16 minutes (3)

[0014] The T90 is the time from the water absorption rate X75(%) when the pressure-sensitive adhesive layer is stored for 360 minutes under conditions of 23°C and 75% RH to half the water absorption rate X90(%) when the pressure-sensitive adhesive layer is stored for 360 minutes under conditions of 23°C and 90% RH, and the water content changes (increases) most rapidly until the half value is reached. Therefore, the longer the T90, the slower the speed of absorbing water, and the more rapid the change in adhesive strength can be prevented even if the environment changes. The T90 satisfies the above formula (3), that is, the T90 is 16 minutes or more, which is preferable in that the rapid change in adhesive strength due to environmental changes can be prevented and a highly reliable adhesive layer can be obtained. In addition, it is also preferable in that the change in adhesive strength due to the storage environment immediately after film formation is small, and an adhesive layer with excellent productivity can be obtained.

[0015] In the pressure-sensitive adhesive composition of the present invention, when the time required for the pressure-sensitive adhesive layer to reach half of the water absorption rate X25 (%) when stored for 240 minutes under conditions of 23°C and 25% RH from an absolutely dry state is defined as T25 (min), it is preferable that the pressure-sensitive adhesive composition satisfies the following formula (4): T90 / T25≧1.0 (4)

[0016] The T90 / T25 preferably satisfies the above formula (4), i.e., the T90 / T25 is preferably 1.0 or more. The higher the humidity condition, the slower the speed at which the adhesive layer absorbs moisture, and the adhesive layer can be prevented from undergoing a sudden change in adhesive strength due to environmental changes, making it usable in various environments. The configuration in which the T90 / T25 satisfies the above formula (4) is preferable in that it is possible to prevent a sudden change in adhesive strength due to environmental changes, and it is possible to obtain an adhesive layer that is highly reliable and usable in various environments. It is also preferable in that it is possible to obtain an adhesive layer that shows little change in adhesive strength due to the storage environment immediately after film formation, and has excellent productivity.

[0017] The second aspect of the present invention provides a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present invention. In this specification, the pressure-sensitive adhesive layer of the second aspect of the present invention may be referred to as the "pressure-sensitive adhesive layer of the present invention". The pressure-sensitive adhesive layer of the present invention is formed from the pressure-sensitive adhesive composition of the present invention, and is therefore preferred in terms of high reliability with stable adhesive strength even when the environment changes, small change in adhesive strength due to storage environment immediately after film formation, and excellent productivity.

[0018] The third aspect of the present invention provides a pressure-sensitive adhesive sheet having the pressure-sensitive adhesive layer of the present invention. In this specification, the pressure-sensitive adhesive sheet of the third aspect of the present invention may be referred to as the "pressure-sensitive adhesive sheet of the present invention." The pressure-sensitive adhesive sheet of the present invention has the pressure-sensitive adhesive layer of the present invention, and therefore has high reliability with stable adhesive strength even when the environment changes, and is preferable in terms of small change in adhesive strength due to the storage environment immediately after the pressure-sensitive adhesive layer is formed, and excellent productivity.

[0019] The fourth aspect of the present invention provides an optical member with a pressure-sensitive adhesive layer, in which the pressure-sensitive adhesive sheet of the present invention is attached to at least one surface of the optical member. In this specification, the pressure-sensitive adhesive layer-attached optical member of the fourth aspect of the present invention may be referred to as the "pressure-sensitive adhesive layer-attached optical member of the present invention". The pressure-sensitive adhesive layer-attached optical member of the present invention is preferable from the viewpoint of high reliability with stable adhesive strength even when the environment changes, since it has the pressure-sensitive adhesive layer of the present invention.

[0020] The fifth aspect of the present invention provides an image display device having the pressure-sensitive adhesive layer-attached optical member of the present invention. In this specification, the image display device of the fifth aspect of the present invention may be referred to as the "image display device of the present invention." The image display device of the present invention may be a touch panel.

[0021] The image display device and touch panel of the present invention are preferable from the viewpoints of high reliability with stable adhesive strength even under environmental changes and excellent durability, since optical members are bonded with the pressure-sensitive adhesive layer of the present invention. Effect of the Invention

[0022] The pressure-sensitive adhesive composition of the present invention can form a pressure-sensitive adhesive layer that has high reliability and stable adhesive strength even when the environment changes, and exhibits little change in adhesive strength due to the storage environment immediately after film formation, and has excellent productivity. Therefore, by laminating optical members using a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition of the present invention, it is possible to efficiently produce high-performance image display devices and touch panels that have high reliability and stable adhesive strength even when the environment changes, and are excellent in durability. [Brief description of the drawings]

[0023] [Figure 1] FIG. 1 is a schematic diagram showing a specific example of a preferred embodiment of the pressure-sensitive adhesive sheet of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing a specific example of a preferred embodiment of the pressure-sensitive adhesive layer-attached optical member of the present invention. [Diagram 3] FIG. 3 is a schematic diagram showing a specific example of a preferred embodiment of the image display device of the present invention. [Figure 4] FIG. 4 is a schematic diagram showing a specific example of a preferred embodiment of the touch panel of the present invention. [Diagram 5] 5 is a graph showing the results of adhesive strength measurements in the present examples and comparative examples, where (a) is the result of Example 1, (b) is the result of Example 2, (c) is the result of Example 3, and (d) is the result of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] [1. Pressure-sensitive adhesive composition and pressure-sensitive adhesive layer] The pressure-sensitive adhesive composition of the present invention is a pressure-sensitive adhesive composition for forming a pressure-sensitive adhesive layer used for adhering an optical member of an image display device, When the water absorption rate of the pressure-sensitive adhesive layer when stored for 360 minutes under conditions of 23° C. and 90% RH is taken as X90(%), it satisfies the following formula (1). X90≦1.5% (1)

[0025] The pressure-sensitive adhesive composition of the present invention is used for forming a pressure-sensitive adhesive layer used for adhering optical members such as polarizing films, retardation films, optical compensation films, touch sensor films, and cover films to image display panels or for adhering these optical members to each other in image display devices such as liquid crystal displays (LCDs) and organic light-emitting diode displays (OLEDs) and touch panels in which a touch sensor is incorporated into these image display devices. In this specification, the term "image display device" includes a "touch panel" unless otherwise specified.

[0026] The adhesive composition of the present invention is particularly suitable for use in vehicle-mounted image display devices and touch panels. Vehicle-mounted displays are often exposed to harsh environments such as high temperature, high humidity, and sunlight for long periods of time, and are required to have high reliability such that properties such as adhesive strength are unlikely to change even when the environment changes. In addition, if the adhesive strength changes significantly depending on the storage environment immediately after the adhesive layer is formed, it is necessary to store the adhesive layer until the adhesive strength stabilizes, which causes a problem of reduced productivity.

[0027] The reason why the adhesive strength changes depending on the environment is thought to be that the amount of moisture absorbed by the adhesive layer causes the adhesive layer to swell and shrink, changing the elastic modulus, and the moisture contained in the adhesive interacts with the polar groups on the adhesive surface, inhibiting the interaction between the polar groups on the adhesive surface and the polar groups on the adherend surface, affecting the adhesive strength. Therefore, if the change in the amount of moisture absorbed by the adhesive layer is small even when the environment changes, the effect on the adhesive strength will be small, and it is thought that a highly reliable adhesive layer can be obtained.

[0028] The water absorption rate X90 is the proportion of water absorbed by the pressure-sensitive adhesive layer of the present invention in a high humidity environment of 90% RH. If the water absorption rate X90 is high, the pressure-sensitive adhesive layer will swell and shrink due to environmental changes, and the moisture contained in the pressure-sensitive adhesive may inhibit the interaction between the polar group on the pressure-sensitive adhesive surface and the polar group on the adherend surface, affecting the adhesive strength. The water absorption rate X90 satisfies the above formula (1), that is, the water absorption rate X90 is 1.5% or less, which is preferable in that a highly reliable pressure-sensitive adhesive layer whose adhesive strength is unlikely to change due to environmental changes such as temperature and humidity can be obtained. It is also preferable in that a pressure-sensitive adhesive layer whose adhesive strength changes little due to the storage environment immediately after film formation and which has excellent productivity can be obtained.

[0029] The water absorption rate X90 is preferably 1.4% or less, more preferably 1.3% or less, even more preferably 1.2% or less, and may be 1.1% or less, in order to obtain a pressure-sensitive adhesive layer having high reliability in that the adhesive strength is unlikely to change due to environmental changes, in which the adhesive strength changes little due to the storage environment immediately after film formation, and in which the productivity is excellent. The lower limit of the water absorption rate X90 is not particularly limited, and the lower the better, but it may be 0.5% or more.

[0030] In the pressure-sensitive adhesive composition of the present invention, when the water absorption rate when the pressure-sensitive adhesive layer of the present invention is stored for 240 minutes under conditions of 23° C. and 25% RH is defined as X25 (%), it is preferable that the following formula (2) is satisfied. X90-X25≦1.5% (2)

[0031] The water absorption rate X25 is the proportion of water absorbed by the adhesive layer in a dry environment of 25% RH, and if the difference from the X90 is large, the amount of water contained in the adhesive layer changes greatly depending on the environment, which also has a large effect on the adhesive strength, and reliability may decrease. The difference between the water absorption rate X90 and the water absorption rate X25 (X90-X25) satisfies the above formula (2), that is, is 1.5% or less, which is preferable in that it provides an adhesive layer that is highly reliable and has adhesive strength that is unlikely to change due to environmental changes such as temperature and humidity, and can be used in various environments. It is also preferable in that it provides an adhesive layer that has little change in adhesive strength due to the storage environment immediately after film formation, and has excellent productivity.

[0032] The difference X90-X25 is preferably 1.4% or less, more preferably 1.3% or less, even more preferably 1.2% or less, and may be 1.1% or less or 1.0% or less, in terms of obtaining a pressure-sensitive adhesive layer with high reliability, in which the adhesive strength is unlikely to change due to environmental changes, usable in various environments, and with little change in adhesive strength due to storage environment immediately after film formation, and with excellent productivity. The lower limit of the difference X90-X25 is not particularly limited, and the lower the better, but it may be 0.5% or more.

[0033] In the pressure-sensitive adhesive composition of the present invention, when the time required for the pressure-sensitive adhesive layer to reach half of the water absorption rate X90(%) when stored for 360 minutes under conditions of 23°C and 75% RH from the water absorption rate X75(%) when stored for 360 minutes under conditions of 23°C and 90% RH is defined as T90 (min), it is preferable that the pressure-sensitive adhesive composition satisfies the following formula (3): T90≧16 minutes (3)

[0034] Here, the "half value" refers to the half value of the water absorption rate from X75 to X90, that is, the water absorption rate (%) represented by the formula: (X90-X75) / 2. The "time to reach half value" refers to the time from the start of storage under conditions of 23°C and 90% RH until the above "half value" is reached. The same applies to the "half value" for T25, T50, and T75 described below.

[0035] The T90 is the time from the water absorption rate X75(%) when the pressure-sensitive adhesive layer is stored for 360 minutes under conditions of 23°C and 75% RH to half the water absorption rate X90(%) when the pressure-sensitive adhesive layer is stored for 360 minutes under conditions of 23°C and 90% RH, and the water content changes (increases) most rapidly until the half value is reached. Therefore, the longer the T90, the slower the speed of absorbing water, and the more rapid the change in adhesive strength can be prevented even if the environment changes. The T90 satisfies the above formula (3), that is, the T90 is 16 minutes or more, which is preferable in that the rapid change in adhesive strength due to environmental changes can be prevented and a highly reliable adhesive layer can be obtained. In addition, it is also preferable in that the change in adhesive strength due to the storage environment immediately after film formation is small, and an adhesive layer with excellent productivity can be obtained.

[0036] The T90 is preferably 17 minutes or more, more preferably 18 minutes or more, even more preferably 19 minutes or more, and may be 20 minutes or more, in order to prevent a sudden change in adhesive strength due to environmental changes, to obtain a highly reliable adhesive layer that shows little change in adhesive strength due to storage environment immediately after film formation and has excellent productivity. The upper limit of the T90 is not particularly limited, and the longer the better, but it may be 60 minutes or less.

[0037] In the pressure-sensitive adhesive composition of the present invention, when the time required for the pressure-sensitive adhesive layer to reach half of the water absorption rate X25 (%) when stored for 240 minutes under conditions of 23°C and 25% RH from an absolutely dry state is defined as T25 (min), it is preferable that the pressure-sensitive adhesive composition satisfies the following formula (4): T90 / T25≧1.0 (4)

[0038] Here, the above-mentioned "absolutely dry state" means a state in which the weight of the pressure-sensitive adhesive layer does not decrease even if the pressure-sensitive adhesive layer is left to stand under dry conditions. In this specification, the pressure-sensitive adhesive layer stored for 60 minutes under conditions of 150°C and 0% RH and then stored for 240 minutes under conditions of 23°C and 0% RH is considered to be in an "absolutely dry state" because the weight of the pressure-sensitive adhesive layer does not decrease substantially even if the pressure-sensitive adhesive layer is stored for a longer period of time.

[0039] The higher the humidity condition, the slower the adhesive layer absorbs moisture, and the more rapid changes in adhesive strength caused by environmental changes can be prevented, making it possible to use the adhesive in various environments. The T90 / T25 satisfies the above formula (4), i.e., the T90 / T25 is 1.0 or more, which is preferable in that it is possible to prevent rapid changes in adhesive strength caused by environmental changes, and it is possible to obtain an adhesive layer that is highly reliable and can be used in various environments. It is also preferable in that it is possible to obtain an adhesive layer that has little change in adhesive strength caused by storage environment immediately after film formation, and has excellent productivity.

[0040] The T90 / T25 is preferably 1.1 or more, more preferably 1.2 or more, even more preferably 1.3 or more, and may be 1.4 or more, in that it can prevent a sudden change in adhesive strength due to environmental changes, is highly reliable, can be used in various environments, changes in adhesive strength due to storage environment immediately after film formation are small, and an adhesive layer with excellent productivity can be obtained. The upper limit of the T90 / T25 is not particularly limited, and the higher the better, but it may be 2.0 or less.

[0041] The water absorption rate X25 is preferably 0.3% or less, more preferably 0.25% or less, even more preferably 0.2% or less, and may be 0.15% or less, in order to obtain a highly reliable adhesive layer with adhesive strength that is unlikely to change due to environmental changes, with little change in adhesive strength due to storage environment immediately after film formation, and with excellent productivity. The lower limit of the water absorption rate X25 is not particularly limited, and the lower the better, but it may be 0.01% or more.

[0042] When the water absorption rate of the pressure-sensitive adhesive layer of the present invention is X50 (%) when it is stored for 240 minutes under the condition of 23°C and 50% RH, the water absorption rate X50 is preferably 0.8% or less, more preferably 0.7% or less, even more preferably 0.6% or less, and may be 0.5% or less, in order to obtain a pressure-sensitive adhesive layer having high reliability in which the adhesive strength is unlikely to change due to environmental changes, in which the adhesive strength changes little due to the storage environment immediately after film formation, and in which the productivity is excellent. The lower limit of the water absorption rate X50 is not particularly limited, and the lower the better, but it may be 0.1% or more.

[0043] When the water absorption rate of the pressure-sensitive adhesive layer of the present invention is X75 (%) when it is stored for 360 minutes under the condition of 23°C and 75% RH, the water absorption rate X75 is preferably 1.2% or less, more preferably 1.1% or less, even more preferably 1.0% or less, and may be 0.9% or less, or 0.8% or less, in order to obtain a pressure-sensitive adhesive layer having high reliability in which the adhesive strength is not easily changed by environmental changes, a small change in the adhesive strength due to the storage environment immediately after film formation, and excellent productivity. The lower limit of the water absorption rate X75 is not particularly limited, and the lower the better, but it may be 0.3% or more.

[0044] The T25 is preferably 16 minutes or more, more preferably 17 minutes or more, even more preferably 18 minutes or more, and may be 19 minutes or more, or may be 20 minutes or more, in that a rapid change in adhesive strength due to environmental changes can be prevented, a high reliability can be obtained, a change in adhesive strength due to storage environment immediately after film formation is small, and an adhesive layer with excellent productivity can be obtained. The upper limit of the T25 is not particularly limited, and the longer the better, but it may be 60 minutes or less.

[0045] When the time from the water absorption rate X25(%) when the pressure-sensitive adhesive layer is stored for 240 minutes under the condition of 23°C and 25%RH to the half value of the water absorption rate X50(%) when the pressure-sensitive adhesive layer is stored for 240 minutes under the condition of 23°C and 50%RH is defined as T50(min), the pressure-sensitive adhesive layer can be prevented from undergoing a sudden change in adhesive strength due to environmental changes, is highly reliable, has a small change in adhesive strength due to the storage environment immediately after film formation, and is excellent in productivity. In this respect, the T50 is preferably 16 minutes or more, more preferably 17 minutes or more, even more preferably 18 minutes or more, and may be 19 minutes or more, or 20 minutes or more. The upper limit of the T50 is not particularly limited, and the longer the better, but it may be 60 minutes or less.

[0046] When the time from the water absorption rate X50 (%) when the pressure-sensitive adhesive layer is stored for 240 minutes under the condition of 23°C and 50% RH to the half value of the water absorption rate X75 (%) when the pressure-sensitive adhesive layer is stored for 360 minutes under the condition of 23°C and 75% RH is defined as T75 (min), the pressure-sensitive adhesive layer can be prevented from undergoing a sudden change in adhesive strength due to environmental changes, is highly reliable, has a small change in adhesive strength due to the storage environment immediately after film formation, and is excellent in productivity. In this respect, T75 is preferably 16 minutes or more, more preferably 17 minutes or more, even more preferably 18 minutes or more, and may be 19 minutes or more, or 20 minutes or more. The upper limit of T75 is not particularly limited, and the longer the better, but it may be 60 minutes or less.

[0047] In the pressure-sensitive adhesive composition of the present invention, the water absorption rates X90, X25, X50, and X75 are determined as the rate of increase in the weight of the pressure-sensitive adhesive layer at the end of each storage condition, with the weight of the pressure-sensitive adhesive layer in an absolutely dry state being 100%.

[0048] When the water absorption rates X90, X25, X50, and X75 reach a maximum value before reaching the end point of each storage condition, they indicate the saturated water absorption rate under each storage condition. On the other hand, when the water absorption rates do not reach a maximum value before reaching the end point of each storage condition, the end point of each storage condition is the maximum value, not the saturated water absorption rate. The water absorption rates X90, X25, X50, and X75 are preferably not the saturated water absorption rate because the water absorption speed is slow and a sudden change in the physical properties of the pressure-sensitive adhesive layer is prevented, but may be the saturated water absorption rate.

[0049] In the pressure-sensitive adhesive composition of the present invention, the water absorption rates X90, X25, X50, X75, X90-X25, T90, T25, T50, T75 and T90 / T25 are specifically measured by the water absorption rate and water absorption rate measurements in the Examples described later, and can be adjusted, for example, by the monomer composition (type, content, composition, etc. of functional group-containing monomer) of the base polymer (particularly, acrylic polymer) described later, the type and amount of crosslinking agent, the type and amount of hydrogenated polyolefin resin, etc.

[0050] When the initial adhesive strength of the pressure-sensitive adhesive sheet of the present invention against a glass plate at 23°C, a tensile speed of 300 mm / min, a peel angle of 180°, and a peel length of 50 mm is defined as Y0 (N / 20 mm), Y0 is not particularly limited, but from the viewpoint of small change in adhesive strength in the storage environment and excellent productivity, it is preferably 16 N / 20 mm or more, more preferably 17 N / 20 mm or more, even more preferably 18 N / 20 mm or more, and even more preferably 19 N / 20 mm or more. The upper limit of Y0 is not particularly limited, but may be, for example, 60 N / 20 mm or less. In this specification, the "initial adhesive strength" refers to a strength measured within 12 hours after the pressure-sensitive adhesive layer is formed.

[0051] When the adhesive sheet of the present invention is stored for 48 hours under conditions of 23°C and 50% RH after the measurement of the initial adhesive strength Y0, and the adhesive strength of the adhesive sheet against a glass plate at 23°C, a pulling speed of 300mm / min, a peeling angle of 180°, and a peeling length of 50mm is defined as Y48 (N / 20mm), Y48 is not particularly limited, but from the viewpoint of small change in adhesive strength in the storage environment and excellent productivity, it is preferably 16N / 20mm or more, more preferably 17N / 20mm or more, even more preferably 18N / 20mm or more, and even more preferably 19N / 20mm or more. The upper limit of Y48 is not particularly limited, but may be, for example, 60N / 20mm or less.

[0052] The rate of change in adhesive strength Y48 relative to the initial adhesive strength Y0 of the adhesive sheet of the present invention ((Y0-Y48) / Y0x100) (%) is not particularly limited, but from the viewpoint of small change in adhesive strength in the storage environment and excellent productivity, it is preferably within ±10%, more preferably within ±9%, even more preferably within ±8%, and may be within ±7%.

[0053] In the pressure-sensitive adhesive composition of the present invention, the above-mentioned adhesive strengths Y0, Y48 and their rate of change are specifically measured by the adhesive strength measurement in the Examples described later, and can be adjusted, for example, by the monomer composition (type, content, composition, etc. of functional group-containing monomer) of the base polymer (particularly, acrylic polymer) described later, the type and amount of crosslinking agent, the type and amount of hydrogenated polyolefin resin, etc.

[0054] The pressure-sensitive adhesive layer of the present invention is not particularly limited, but from the viewpoint of preventing malfunction of a touch panel having the pressure-sensitive adhesive layer, it is preferable that the dielectric constant is controlled to be low. The pressure-sensitive adhesive layer of the present invention preferably has a dielectric constant of 4 or less at a frequency of 100 kHz, more preferably 3.9 or less, and even more preferably 3.8 or less. The lower limit of the dielectric constant at a frequency of 100 kHz is not particularly limited, but is preferably 2.3 or more, more preferably 2.4 or more, and even more preferably 2.5 or more.

[0055] The dielectric constant of the pressure-sensitive adhesive layer of the present invention is measured in accordance with JIS K 6911, and can be adjusted, for example, by the monomer composition (type, content, composition, etc. of functional group-containing monomer) of the base polymer (particularly, acrylic polymer) described below, the type and amount of crosslinking agent, the type and amount of hydrogenated polyolefin resin, etc.

[0056] The pressure-sensitive adhesive layer of the present invention has excellent transparency since it is used for adhering optical members of an image display device, and therefore has excellent visibility and appearance through the pressure-sensitive adhesive layer of the present invention.

[0057] The haze of the pressure-sensitive adhesive layer of the present invention (based on JIS K7136) is not particularly limited, but is preferably 1.0% or less, more preferably 0.8% or less. When the haze is 1.0% or less, excellent transparency and excellent appearance are obtained, which is preferable. The lower limit of the haze is not particularly limited, but is theoretically 0%, and may be more than 0.01% in practical use. The haze can be measured, for example, by forming a pressure-sensitive adhesive layer (thickness: 100 μm), leaving it at normal conditions (23° C., 50% RH) for at least 24 hours, and then bonding it to a slide glass (for example, one with a total light transmittance of 92% and a haze of 0.2%) as a sample, using a haze meter (manufactured by Murakami Color Research Laboratory Co., Ltd., product name "HM-150N") or an equivalent.

[0058] The total light transmittance (according to JIS K7361-1) in the visible light wavelength region of the pressure-sensitive adhesive layer of the present invention is not particularly limited, but is preferably 90% or more, more preferably 91% or more, and even more preferably 92% or more. If the total light transmittance is 90% or more, excellent transparency and excellent appearance can be obtained, which is preferable. The upper limit of the total light transmittance is not particularly limited, but theoretically, it is a value obtained by subtracting the light loss (Fresnel loss) caused by reflection at the air interface from 100%, and in practical use, it may be 95% or less. The total light transmittance can be measured, for example, by forming a pressure-sensitive adhesive layer (thickness: 100 μm), leaving it at normal conditions (23 ° C., 50% RH) for at least 24 hours, peeling off a release liner if one is present, and bonding it to a slide glass (for example, one with a total light transmittance of 92% and a haze of 0.2%) as a sample, using a haze meter (manufactured by Murakami Color Research Laboratory Co., Ltd., product name "HM-150N") or an equivalent.

[0059] The thickness of the pressure-sensitive adhesive layer of the present invention is not particularly limited, but is preferably 12 to 350 μm, more preferably 12 to 300 μm. If the thickness is more than a certain level, it is preferable in that in a touch panel to which an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is attached, the stress with the metal wiring can be sufficiently relaxed to prevent display unevenness. In addition, if the thickness is less than a certain level, it is particularly preferable in that the handling property and manufacturability are excellent.

[0060] The method for producing the pressure-sensitive adhesive layer of the present invention is not particularly limited. For example, the pressure-sensitive adhesive composition (precursor composition) of the present invention is prepared, and applied (coated) onto a substrate or a release liner, and if necessary, irradiation with active energy rays, drying by heating, etc. may be performed.

[0061] The pressure-sensitive adhesive composition may be applied (coated) by a known coating method, for example, a coater such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater, a spray coater, a comma coater, or a direct coater.

[0062] The adhesive composition of the present invention may have any form, for example, an emulsion type, a hot melt type, a solventless type (active energy ray curing type, for example, a monomer mixture, or a monomer mixture and a partial polymer thereof, etc.), etc. are mentioned. In particular, it is preferable that the adhesive composition of the present invention is not a solvent type. This is because when an adhesive layer is obtained using a solvent type adhesive composition, defects in appearance such as yuzu skin are likely to occur. Incidentally, "yuzu skin" refers to a phenomenon in which unevenness like the skin of "yuzu", a type of citrus fruit, occurs. In addition, from the viewpoint of obtaining an adhesive layer with excellent appearance, it is preferable that the adhesive composition of the present invention is an active energy ray curing type. In this specification, the adhesive composition means a composition used for forming an adhesive layer, and includes the meaning of a composition used for forming an adhesive.

[0063] As described above, the pressure-sensitive adhesive composition of the present invention is preferably not a solvent-based composition, that is, it is preferable that the pressure-sensitive adhesive composition does not contain or substantially does not contain an organic solvent. The organic solvent is not particularly limited as long as it is an organic compound that can be used as a solvent, and examples thereof include hydrocarbon solvents such as cyclohexane, hexane, heptane, etc., aromatic solvents such as toluene, xylene, etc., ester solvents such as ethyl acetate, methyl acetate, etc., ketone solvents such as acetone, methyl ethyl ketone, etc., alcohol solvents such as methanol, ethanol, butanol, isopropyl alcohol, etc. The organic solvent may be a mixed solvent containing two or more organic solvents.

[0064] In the pressure-sensitive adhesive composition of the present invention, "substantially free of organic solvent" means that the organic solvent is not actively blended, except in cases where the organic solvent is inevitably mixed in. Specifically, a pressure-sensitive adhesive composition having an organic solvent content of 1.0% by weight or less (preferably 0.5% by weight or less, more preferably 0.2% by weight or less) relative to the total amount of the pressure-sensitive adhesive composition (total weight, 100% by weight) can be said to be substantially free of organic solvent.

[0065] The pressure-sensitive adhesive composition of the present invention preferably has a halogen ion concentration of 50 ppm or less. This configuration is preferable from the viewpoint of obtaining a corrosion prevention effect on metal wiring in a touch panel to which an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is attached. The content of halogen ions is preferably 50 ppm or less (e.g., 0 to 50 ppm) based on the total amount of the pressure-sensitive adhesive composition, more preferably 40 ppm or less (e.g., 0 to 40 ppm), and even more preferably 30 ppm or less (e.g., 0 to 30 ppm), so that it can be said that the pressure-sensitive adhesive composition does not substantially contain any halogen ions.

[0066] The pressure-sensitive adhesive composition of the present invention preferably does not contain or substantially does not contain a carboxyl group-containing monomer as a monomer component constituting a polymer. Therefore, in a touch panel to which an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is attached, a corrosion prevention effect on the metal wiring can be obtained. The content of the carboxyl group-containing monomer is 1 ng / cm based on the total amount of the pressure-sensitive adhesive composition. 2 Less than (e.g., 0 to 1 ng / cm 2 ) is preferred, and 0.8 ng / cm is more preferred. 2 Less than (e.g., 0 to 0.8 ng / cm 2 ), more preferably 0.5 ng / cm 2 Less than (e.g., 0 to 0.5 ng / cm 2 ) is not substantially contained. Examples of the carboxyl group-containing monomer include (meth)acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, and the like. The carboxyl group-containing monomer also includes, for example, acid anhydride group-containing monomers such as maleic anhydride and itaconic anhydride.

[0067] The halogen ion content and carboxyl group-containing monomer content of the pressure-sensitive adhesive composition of the present invention can be measured by an energy dispersive X-ray fluorescence analyzer, ion chromatography, or the like, and can be adjusted, for example, by the monomer composition (type, content, composition, etc. of functional group-containing monomer) of the base polymer (particularly, acrylic polymer) described below, the type and amount of crosslinking agent, the type and amount of hydrogenated polyolefin resin, etc.

[0068] The base polymer contained in the pressure-sensitive adhesive composition of the present invention is not particularly limited, but examples thereof include an acrylic polymer contained as a base polymer in an acrylic pressure-sensitive adhesive layer, a rubber polymer contained as a base polymer in a rubber pressure-sensitive adhesive layer (such as a natural rubber pressure-sensitive adhesive layer or a synthetic rubber pressure-sensitive adhesive layer), a silicone polymer contained as a base polymer in a silicone pressure-sensitive adhesive layer, a polyester polymer contained as a base polymer in a polyester pressure-sensitive adhesive layer, a urethane polymer contained as a base polymer in a urethane pressure-sensitive adhesive layer, a polyamide polymer contained as a base polymer in a polyamide pressure-sensitive adhesive layer, an epoxy polymer contained as a base polymer in an epoxy pressure-sensitive adhesive layer, a vinyl alkyl ether polymer contained as a base polymer in a vinyl alkyl ether pressure-sensitive adhesive layer, and a fluorine polymer contained as a base polymer in a fluorine pressure-sensitive adhesive layer. Among these, the base polymer is preferably an acrylic polymer in terms of transparency, weather resistance, adhesion reliability, and ease of functional design of the pressure-sensitive adhesive layer due to the wide variety of monomers. In other words, the pressure-sensitive adhesive composition of the present invention is preferably an acrylic pressure-sensitive adhesive composition containing an acrylic polymer described below as a base polymer. The base polymers may be used alone or in combination of two or more.

[0069] The content of the above-mentioned base polymer in the pressure-sensitive adhesive composition of the present invention is not particularly limited, but is preferably 75% by weight or more (for example, 75 to 99.9% by weight), and more preferably 85% by weight or more (for example, 85 to 99.9% by weight).

[0070] When the pressure-sensitive adhesive composition of the present invention is an acrylic pressure-sensitive adhesive composition containing an acrylic polymer as a base polymer, it is referred to as "the acrylic pressure-sensitive adhesive composition of the present invention". The acrylic pressure-sensitive adhesive composition of the present invention will be described in detail below, but the present invention is not limited thereto.

[0071] [1-1. Acrylic polymers] The acrylic pressure-sensitive adhesive composition of the present invention is a pressure-sensitive adhesive composition containing an acrylic polymer as a base polymer. The acrylic polymer may be used alone or in combination of two or more kinds. The acrylic pressure-sensitive adhesive composition of the present invention may contain, in addition to the acrylic polymer, a hydrogenated polyolefin resin, a polyfunctional (meth)acrylate, a silane coupling agent, and other additives, which will be described later.

[0072] The content of the acrylic polymer is not particularly limited, but is preferably 60% by weight or more (e.g., 60 to 99.9% by weight) relative to the total amount of the acrylic pressure-sensitive adhesive composition of the present invention (total weight, 100% by weight), and more preferably 70% by weight or more (e.g., 70 to 99.9% by weight).

[0073] The acrylic adhesive composition of the present invention forming an adhesive layer containing an acrylic polymer as a main component is not particularly limited, but examples thereof include a composition containing an acrylic polymer as an essential component; a mixture of monomer components constituting an acrylic polymer (sometimes referred to as a "monomer mixture") or a composition containing a partial polymer thereof as an essential component, and the like. Although not particularly limited, examples of the former include so-called water-dispersed compositions (emulsion-type compositions), and examples of the latter include so-called active energy ray-curable compositions. Among them, the acrylic adhesive composition of the present invention is preferably a composition containing a monomer mixture or a partial polymer thereof as an essential component.

[0074] In this specification, the above-mentioned "mixture of monomer components" includes a case where the mixture is composed of a single monomer component and a case where the mixture is composed of two or more monomer components. Also, the above-mentioned "partially polymerized product of the mixture of monomer components" means a composition in which one or more of the constituent monomer components of the above-mentioned "mixture of monomer components" are partially polymerized. In this specification, unless otherwise specified, the term "acrylic polymer" includes "acrylic polymer," "a mixture of monomer components constituting an acrylic polymer," and "a partial polymer of a mixture of monomer components constituting an acrylic polymer."

[0075] An acrylic polymer is a polymer containing an acrylic monomer as an essential monomer unit. In other words, an acrylic polymer is a polymer containing a constituent unit derived from an acrylic monomer as a constituent unit. In other words, an acrylic polymer is a polymer constituted (formed) with an acrylic monomer as an essential monomer component. In this specification, "(meth)acrylic" refers to either one or both of "acrylic" and "methacrylic", and the same applies to the others. The weight average molecular weight of the acrylic polymer is not particularly limited, but is preferably 100,000 to 5,000,000.

[0076] In the acrylic pressure-sensitive adhesive composition of the present invention, the acrylic polymer is preferably a polymer containing, as a monomer unit, a (meth)acrylic acid alkyl ester having a linear or branched alkyl group (hereinafter, sometimes simply referred to as "(meth)acrylic acid alkyl ester").

[0077] Examples of the (meth)acrylic acid alkyl ester include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate (n-butyl (meth)acrylate), isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, Examples of the (meth)acrylic acid alkyl ester include those having an alkyl group having 1 to 24 carbon atoms, such as nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. The (meth)acrylic acid alkyl ester may be used alone or in combination of two or more kinds.

[0078] As the (meth)acrylic acid alkyl ester, an acrylic acid alkyl ester is more preferable than a methacrylic acid alkyl ester in that it can shorten the polymerization time of the acrylic polymer and improve the productivity. In particular, when the acrylic polymer of the present invention is cured by radiation polymerization, an acrylic acid alkyl ester is suitable.

[0079] Among these, from the viewpoints of obtaining strong adhesion and adjusting residual stress, the (meth)acrylic acid alkyl ester is preferably a (meth)acrylic acid alkyl ester having an alkyl group with 1 to 18 carbon atoms, more preferably methyl methacrylate (MMA), butyl acrylate (BA), 2-ethylhexyl acrylate (2EHA), and isostearyl acrylate (ISTA), with 2-ethylhexyl acrylate (2EHA) and isostearyl acrylate (ISTA) being more preferred.

[0080] The content (proportion) of the (meth)acrylic acid alkyl ester in all monomer units of the acrylic polymer (total amount of monomer components constituting the acrylic polymer) is not particularly limited, but from the viewpoint of improving durability and obtaining high adhesion reliability, it is preferably 30 to 90 parts by weight, more preferably 35 to 85 parts by weight, and even more preferably 40 to 80 parts by weight, relative to the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer.

[0081] In this specification, the term "the total amount of monomer components constituting the acrylic polymer" is intended to include monomer components added to the acrylic pressure-sensitive adhesive composition of the present invention containing an acrylic polymer for the purpose of adjusting the elastic modulus of the pressure-sensitive adhesive layer or the like.

[0082] As a preferred embodiment of the acrylic pressure-sensitive adhesive composition of the present invention, the acrylic polymer is preferably a polymer containing an alkyl (meth)acrylate ester having an alkyl group having 8 or more carbon atoms (sometimes referred to as "alkyl (meth)acrylate ester (A)") as an essential monomer unit. That is, the acrylic polymer of this embodiment is preferably obtained by polymerizing a monomer component containing an alkyl (meth)acrylate ester having a medium- to long-chain alkyl group such as the alkyl (meth)acrylate ester (A). The acrylic polymer is preferable in that it can realize a highly flexible pressure-sensitive adhesive layer due to the action of the medium- to long-chain alkyl group, and can sufficiently relieve stress with the metal wiring to prevent display unevenness even when an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is bonded.

[0083] In this embodiment, examples of the (meth)acrylic acid alkyl ester (A) include (meth)acrylic acid alkyl esters having an alkyl group with 8 or more carbon atoms (preferably 8 to 24 carbon atoms), such as octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. The (meth)acrylic acid alkyl ester (A) may be used alone or in combination of two or more.

[0084] In this embodiment, as the (meth)acrylic acid alkyl ester (A), an acrylic acid alkyl ester is more preferable than a methacrylic acid alkyl ester in that it can shorten the polymerization time of the acrylic polymer (A) and improve productivity. In particular, when the acrylic polymer of the present invention is cured by radiation polymerization, an acrylic acid alkyl ester is suitable.

[0085] Among them, the (meth)acrylic acid alkyl ester (A) preferably contains a (meth)acrylic acid alkyl ester having a branched alkyl group with 8 or more carbon atoms, and more preferably contains a (meth)acrylic acid alkyl ester having a branched alkyl group with 8 or 9 carbon atoms, in that it can realize a highly flexible adhesive layer, and can prevent display unevenness even when an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is bonded to the adhesive, by sufficiently relaxing the stress with the metal wiring. More preferably, the (meth)acrylic acid alkyl ester contains 2-ethylhexyl (meth)acrylate, and particularly preferably 2-ethylhexyl acrylate (2EHA). The number of carbon atoms in the side chain alkyl group of the branched alkyl group is not particularly limited, but an alkyl group having 1 to 3 carbon atoms (for example, a methyl group, an ethyl group, an n-propyl group, or an isopropyl group) is preferred. The "side chain alkyl group" is an alkyl group that substitutes for the side chain of the carbon chain with the longest carbon number.

[0086] In this embodiment, the content (ratio) of the above-mentioned (meth)acrylic acid alkyl ester (A) in all monomer units of the acrylic polymer (total amount of monomer components constituting the acrylic polymer) is not particularly limited, but is preferably 30 to 99 parts by weight, more preferably 35 to 95 parts by weight, and even more preferably 40 to 90 parts by weight, relative to the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer, in order to realize a highly flexible adhesive layer and to sufficiently relieve stress with the metal wiring even when an optical component (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is bonded thereto, thereby preventing display unevenness.

[0087] In the present embodiment, when the (meth)acrylic acid alkyl ester (A) contains a (meth)acrylic acid alkyl ester having a branched alkyl group having 8 or 9 carbon atoms (hereinafter, in this specification, may be referred to as a (meth)acrylic acid alkyl ester (A1)), it is preferable that the (meth)acrylic acid alkyl ester (A) further contains a (meth)acrylic acid alkyl ester having a branched alkyl group having 10 to 24 carbon atoms (hereinafter, in this specification, may be referred to as a (meth)acrylic acid alkyl ester (A2)).

[0088] In this embodiment, when the (meth)acrylic acid alkyl ester (A) contains a (meth)acrylic acid alkyl ester (A2) in addition to the (meth)acrylic acid alkyl ester (A1), the dielectric constant of the pressure-sensitive adhesive layer of the present invention can be reduced due to the action of the long-chain branched alkyl group, and this is preferable because the pressure-sensitive adhesive layer has a low dielectric constant and can prevent malfunction even when the adhesive layer is attached to an optical component (touch sensor film) on which a metal wiring layer such as metal mesh wiring or silver nanowires is formed.

[0089] The Tg of the homopolymer of the (meth)acrylic acid alkyl ester (A2) is preferably -80 to 0°C, more preferably -70 to -10°C. If the Tg of the homopolymer is -80°C or lower, the elastic modulus of the pressure-sensitive adhesive layer at room temperature may be too low, which is not preferable, and if it exceeds 0°C, the adhesive strength may be reduced, which is not preferable. The Tg of the homopolymer is a value measured by a differential scanning calorimeter (DSC). In addition, the branched alkyl group having 10 to 24 carbon atoms has 10 to 24 carbon atoms because it can satisfy an appropriate low dielectric constant and elastic modulus, but an alkyl (meth)acrylate having a suitable alkyl group can be selected depending on the method for producing the (meth)acrylic polymer. For example, when the (meth)acrylic polymer is produced by solution polymerization or the like, the alkyl group has more preferably 10 to 18 carbon atoms, more preferably 10 to 16 carbon atoms, and even more preferably 10 to 14 carbon atoms. When the acrylic polymer is produced by radiation polymerization or the like, the alkyl group preferably has 12 to 18 carbon atoms, and more preferably has 14 to 18 carbon atoms.

[0090] Examples of (meth)acrylic acid alkyl esters (A2) include isodecyl acrylate (carbon number 10, homopolymer Tg = -60 ° C., hereinafter simply abbreviated as Tg), isodecyl methacrylate (carbon number 10, Tg = -41 ° C.), isomistyryl acrylate (carbon number 14, Tg = -56 ° C.), isostearyl acrylate (carbon number 18, Tg = -18 ° C.), 2-propylheptyl acrylate, isoundecyl acrylate, isododecyl acrylate, isotridecyl acrylate, isopentadecyl acrylate, isohexadecyl acrylate, isoheptadecyl acrylate, and the above-mentioned methacrylate monomers. The (meth)acrylic acid alkyl esters (A2) can be used alone or in combination of two or more.

[0091] Among the branched alkyl groups having 10 to 24 carbon atoms, those having a branched alkyl group such as a t-butyl group at the end of the ester group are particularly preferred in that the molar volume increases, the dipole moment decreases, and a pressure-sensitive adhesive layer having a good balance between the two is obtained. As the branched alkyl group at the end of the ester group, a branched alkyl group having 4 to 6 carbon atoms such as a t-butyl group, a neopentyl group, or a t-pentyl group is preferred, and a t-butyl group is particularly preferred. A preferred example of the (meth)acrylic acid alkyl ester (A2) having a t-butyl group at the end of the ester group is isostearyl acrylate represented by the following formula: [ka]

[0092] In this embodiment, the content (ratio) of the (meth)acrylic acid alkyl ester (A1) in the total monomer units of the acrylic polymer (total amount of monomer components constituting the acrylic polymer) is not particularly limited, but is preferably 30 parts by weight or more, more preferably 35 parts by weight or more, even more preferably 40 parts by weight or more, and may be 45 parts by weight or more, relative to the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer, in order to realize a highly flexible adhesive layer and to prevent display unevenness by sufficiently relaxing the stress with the metal wiring even when an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is attached. In addition, the content is preferably 70 parts by weight or less, more preferably 65 parts by weight or less, and even more preferably 60 parts by weight or less, in order to prevent malfunction by reducing the dielectric constant of the adhesive layer.

[0093] In this embodiment, the content (ratio) of the (meth)acrylic acid alkyl ester (A2) in all monomer units of the acrylic polymer (total amount of monomer components constituting the acrylic polymer: 100 parts by weight) is not particularly limited, but from the viewpoint of reducing the dielectric constant of the adhesive layer to prevent malfunction, it is preferably 10 parts by weight or more, more preferably 15 parts by weight or more, even more preferably 20 parts by weight or more, and may be 30 parts by weight or more, or 40 parts by weight or more. In addition, the content is preferably 50 parts by weight or less, more preferably 40 parts by weight or less, even more preferably 35 parts by weight or less, and particularly preferably 30 parts by weight or less, in order to realize a highly flexible adhesive layer and to sufficiently relieve stress with the metal wiring even when an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is attached, thereby preventing display unevenness.

[0094] The weight ratio of the (meth)acrylic acid alkyl ester (A1) and the (meth)acrylic acid alkyl ester (A2) in the acrylic polymer of this embodiment ((meth)acrylic acid alkyl ester (A2) / (meth)acrylic acid alkyl ester (A1)) is not particularly limited, but is preferably 2 or less, more preferably 1.5 or less, even more preferably 1 or less, particularly preferably 0.5 or less, and may be 0.45 or less, from the viewpoint of realizing a highly flexible adhesive layer and preventing display unevenness even when an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is bonded, since the stress with the metal wiring can be sufficiently relaxed and display unevenness can be prevented. Also, the above ratio is preferably 0.2 or more, more preferably 0.25 or more, even more preferably 0.3 or more, and may be 0.35 or more. In addition, the above ratio is preferably 0.2 or more, more preferably 0.25 or more, even more preferably 0.3 or more, and may be 0.35 or more, from the viewpoint of reducing the dielectric constant of the adhesive layer to prevent malfunction.

[0095] In this embodiment, the acrylic polymer may contain a (meth)acrylic acid alkyl ester other than the (meth)acrylic acid alkyl ester (A) (hereinafter, may be referred to as "(meth)acrylic acid alkyl ester (B)") as a monomer component. The (meth)acrylic acid alkyl ester (B) may be a (meth)acrylic acid alkyl ester having a linear or branched alkyl group having 1 to 7 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate (n-butyl (meth)acrylate), isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, etc. The (meth)acrylic acid alkyl ester (B) may be used alone or in combination of two or more.

[0096] In this embodiment, the content (ratio) of the above-mentioned (meth)acrylic acid alkyl ester (B) in all monomer units of the acrylic polymer (total amount of monomer components constituting the acrylic polymer) is not particularly limited, but is preferably 10 parts by weight or less, and more preferably 5 parts by weight or less, relative to the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer, in order to realize a highly flexible adhesive layer and to sufficiently relieve stress with the metal wiring even when an optical component (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is bonded to the adhesive, thereby preventing display unevenness.

[0097] In the acrylic pressure-sensitive adhesive composition of the present invention, the acrylic polymer may contain, as a monomer unit, a copolymerizable functional group-containing monomer (copolymerizable functional group-containing monomer) in addition to the above-mentioned (meth)acrylic acid alkyl ester (including the (meth)acrylic acid alkyl ester (A) and the (meth)acrylic acid alkyl ester (B)). In other words, the acrylic polymer may contain a functional group-containing monomer as a constituent monomer component. The functional group-containing monomer may be used alone or in combination of two or more kinds.

[0098] The content (ratio) of the functional group-containing monomer relative to the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer is not particularly limited, but is preferably 5 to 40 parts by weight, more preferably 10 to 30 parts by weight, and even more preferably 15 to 25 parts by weight, in that it provides a highly reliable adhesive layer in which the adhesive strength is resistant to changes in the environment, the adhesive strength changes little depending on the storage environment immediately after film formation, and the adhesive layer has excellent productivity.

[0099] The functional group-containing monomer is not particularly limited, but from the viewpoints of controlling the above-mentioned various properties of the adhesive layer (particularly, water absorption rate, water absorption speed, etc.) within a predetermined range, obtaining a highly reliable adhesive layer whose adhesive strength is unlikely to change with environmental changes, adhesion reliability, compatibility with various additives such as ultraviolet absorbers, and transparency, preferred examples include monomers having a nitrogen atom in the molecule (referred to as "nitrogen atom-containing monomers") and monomers having a hydroxyl group in the molecule (referred to as "hydroxyl group-containing monomers"). That is, the acrylic polymer preferably contains a nitrogen atom-containing monomer as a constituent unit. The acrylic polymer preferably contains a hydroxyl group-containing monomer as a constituent unit.

[0100] When the acrylic polymer contains a nitrogen atom-containing monomer as a monomer unit, it becomes easier to obtain a suitable cohesive force, which increases the 180° peel adhesion to the glass plate, making it easier to obtain strong adhesion and excellent foaming peel resistance. Furthermore, it becomes easier to obtain a suitable flexibility in the adhesive layer, and the 300% tensile residual stress can be adjusted within a specific range, so that even when an optical component (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is bonded, the stress with the metal wiring can be sufficiently alleviated to prevent display unevenness.

[0101] When the acrylic polymer contains the nitrogen atom-containing monomer as a monomer component constituting the polymer, the ratio of the nitrogen atom-containing monomer in the total monomer components constituting the acrylic polymer (100% by weight) is not particularly limited, but is preferably 1% by weight or more, more preferably 3% by weight or more, even more preferably 5% by weight or more, and may be 10% by weight or more, or 15% by weight or more. When the ratio is 1% by weight or more, it is preferable in that the above-mentioned various properties of the pressure-sensitive adhesive layer (particularly, water absorption rate, water absorption speed, etc.) can be controlled within a predetermined range, and a highly reliable pressure-sensitive adhesive layer whose adhesive strength is not easily changed by environmental changes can be obtained, and high adhesive reliability can be obtained. In addition, the upper limit of the ratio of the nitrogen atom-containing monomer is preferably 30% by weight or less, more preferably 25% by weight or less, and even more preferably 20% by weight or less, in terms of obtaining a pressure-sensitive adhesive layer having moderate flexibility, obtaining a pressure-sensitive adhesive layer having excellent transparency, and controlling the above-mentioned various properties of the pressure-sensitive adhesive layer (particularly, water absorption rate, water absorption speed, etc.) within a predetermined range, and obtaining a highly reliable pressure-sensitive adhesive layer whose adhesive strength is not easily changed by environmental changes.

[0102] When the acrylic polymer contains a hydroxyl group-containing monomer as a monomer unit, the monomer components constituting the polymer are easily polymerized and good cohesive strength is easily obtained, which makes it easier to obtain strong adhesion and excellent foaming and peeling resistance.

[0103] When the acrylic polymer contains the hydroxyl group-containing monomer as a monomer component constituting the polymer, the ratio of the hydroxyl group-containing monomer in the total monomer components (100% by weight) constituting the acrylic polymer is not particularly limited, but is preferably 10% by weight or less. When the acrylic polymer contains a large amount of hydroxyl group-containing monomer, the water absorption of the adhesive layer tends to be high because the hydroxyl group has a high affinity with water. In the acrylic polymer, the ratio of the hydroxyl group-containing monomer is 10% by weight or less, which is preferable in that the pressure-sensitive adhesive layer of the present invention can be obtained by controlling the water absorption rate due to the environment to a low level, and the adhesive strength is highly reliable and does not change easily due to environmental changes, and the adhesive strength changes little due to the storage environment immediately after film formation, and the adhesive layer has excellent productivity.

[0104] The ratio of the hydroxyl group-containing monomer is more preferably 8% by weight or less, and even more preferably 6% by weight or less, in order to obtain a highly reliable adhesive layer in which the adhesive strength is not easily changed by environmental changes, the adhesive strength is less changed by the storage environment immediately after film formation, and the adhesive layer has excellent productivity, by controlling the variation of the water absorption rate due to the environment of the pressure-sensitive adhesive layer of the present invention to a low level. The lower limit of the ratio of the hydroxyl group-containing monomer is not particularly limited, but is preferably 0.5% by weight or more, more preferably 0.8% by weight or more, and even more preferably 1% by weight or more, in order to obtain high adhesion reliability and to become a reaction site with the crosslinking agent.

[0105] The total proportion of the nitrogen atom-containing monomer and the hydroxyl group-containing monomer in the total monomer components (100% by weight) constituting the acrylic polymer is not particularly limited, but is preferably 5% by weight or more, more preferably 10% by weight or more, and even more preferably 15% by weight or more, from the viewpoint of obtaining a highly reliable adhesive layer whose adhesive strength is unlikely to change with environmental changes and obtaining high adhesive reliability. The upper limit of the total proportion is preferably 40% by weight or less, more preferably 30% by weight or less, and even more preferably 25% by weight or less, from the viewpoint of obtaining a sealant layer having moderate flexibility, obtaining a sealant layer having excellent transparency, and easily controlling the above-mentioned various properties of the sealant layer (especially the water absorption rate, water absorption speed, etc.) within a predetermined range.

[0106] The ratio of the nitrogen atom-containing monomer to the hydroxyl group-containing monomer in the acrylic polymer (nitrogen atom-containing monomer / hydroxyl group-containing monomer) is not particularly limited, but is preferably 1 to 50, more preferably 1.5 to 40, even more preferably 2 to 30, and particularly preferably 2 to 25. A configuration in which the ratio is 1 or more is preferable in that it controls the fluctuation in water absorption rate due to the environment of the pressure-sensitive adhesive layer of the present invention to a low level, and thus a highly reliable pressure-sensitive adhesive layer in which the adhesive strength is unlikely to change due to environmental changes, and in which the adhesive strength changes little due to the storage environment immediately after film formation and which is excellent in productivity can be obtained. In addition, a configuration in which the ratio is 50 or less is preferable in that the hydroxyl group derived from the hydroxyl group-containing monomer can be a reaction site for the crosslinking agent described below.

[0107] The acrylic polymer can be obtained by polymerizing the monomer unit (monomer component) by a known or conventional polymerization method.The polymerization method of the acrylic polymer can be, for example, a solution polymerization method, an emulsion polymerization method, a bulk polymerization method, a polymerization method by irradiation with active energy rays (active energy ray polymerization method), etc.Among them, in terms of transparency, water resistance, cost, etc. of the pressure-sensitive adhesive layer, the solution polymerization method and the active energy ray polymerization method are preferred, and the active energy ray polymerization method is more preferred.

[0108] Examples of the active energy rays irradiated during the active energy ray polymerization (photopolymerization) include ionizing radiation such as α rays, β rays, γ rays, neutron rays, and electron beams, and ultraviolet rays, among which ultraviolet rays are particularly preferred. The irradiation energy, irradiation time, irradiation method, and the like of the active energy rays are not particularly limited, and may be any as long as they can activate the photopolymerization initiator and cause a reaction of the monomer components.

[0109] In the polymerization of the acrylic polymer, various common solvents may be used. Examples of such solvents include organic solvents such as esters such as ethyl acetate and n-butyl acetate, aromatic hydrocarbons such as toluene and benzene, aliphatic hydrocarbons such as n-hexane and n-heptane, alicyclic hydrocarbons such as cyclohexane and methylcyclohexane, and ketones such as methyl ethyl ketone and methyl isobutyl ketone. The solvents may be used alone or in combination of two or more.

[0110] In addition, when polymerizing the acrylic polymer, a polymerization initiator such as a thermal polymerization initiator or a photopolymerization initiator (photoinitiator) may be used depending on the type of polymerization reaction. The polymerization initiator may be used alone or in combination of two or more kinds.

[0111] The photopolymerization initiator is not particularly limited, and examples thereof include benzoin ether-based photopolymerization initiators, acetophenone-based photopolymerization initiators, α-ketol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, ketal-based photopolymerization initiators, thioxanthone-based photopolymerization initiators, etc. The photopolymerization initiators may be used alone or in combination of two or more.

[0112] Examples of the benzoin ether-based photopolymerization initiator include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one, and anisole methyl ether. Examples of the acetophenone-based photopolymerization initiator include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 4-phenoxydichloroacetophenone, and 4-(t-butyl)dichloroacetophenone. Examples of the α-ketol-based photopolymerization initiator include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropan-1-one. Examples of the aromatic sulfonyl chloride-based photopolymerization initiator include 2-naphthalenesulfonyl chloride. Examples of the photoactive oxime-based photopolymerization initiator include 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime. Examples of the benzoin-based photopolymerization initiator include benzoin. Examples of the benzyl-based photopolymerization initiator include benzyl. Examples of the benzophenone-based photopolymerization initiator include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexylphenyl ketone. Examples of the ketal-based photopolymerization initiator include benzyl dimethyl ketal. Examples of the thioxanthone-based photopolymerization initiator include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, dodecylthioxanthone, etc.

[0113] The amount of the photopolymerization initiator used is not particularly limited, but is preferably 0.001 to 1 part by weight, and more preferably 0.01 to 0.50 parts by weight, per 100 parts by weight of all monomer units of the acrylic polymer (total amount of monomer components constituting the acrylic polymer).

[0114] The thermal polymerization initiator is not particularly limited, but examples thereof include azo polymerization initiators, peroxide polymerization initiators (e.g., dibenzoyl peroxide, tert-butyl permaleate, etc.), redox polymerization initiators, etc. Among them, the azo polymerization initiators disclosed in JP-A-2002-69411 are preferred. Examples of the azo polymerization initiators include 2,2'-azobisisobutyronitrile (hereinafter sometimes referred to as "AIBN"), 2,2'-azobis-2-methylbutyronitrile (hereinafter sometimes referred to as "AMBN"), 2,2'-azobis(2-methylpropionate) dimethyl, and 4,4'-azobis-4-cyanovaleric acid.

[0115] The amount of the thermal polymerization initiator used is not particularly limited. For example, in the case of the azo-based polymerization initiator, the amount is preferably 0.05 to 0.5 parts by weight, and more preferably 0.1 to 0.3 parts by weight, per 100 parts by weight of all monomer units of the acrylic polymer (total amount of monomer components constituting the acrylic polymer).

[0116] [1-2. Hydroxyl-containing monomers] The hydroxyl group-containing monomer means a monomer having at least one hydroxyl group in the molecule. A monomer having at least one hydroxyl group and at least one carboxyl group in the molecule is a carboxyl group-containing monomer, but not a hydroxyl group-containing monomer. The hydroxyl group-containing monomer is not particularly limited, but specifically includes, for example, hydroxyl group-containing (meth)acrylic acid esters such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl) (meth)acrylate; vinyl alcohol, allyl alcohol, and the like. Among them, the hydroxyl group-containing monomer is preferably a hydroxyl group-containing (meth)acrylic acid ester, more preferably 2-hydroxyethyl acrylate (HEA), 2-hydroxypropyl acrylate (HPA), or 4-hydroxybutyl acrylate (4HBA), from the viewpoint of easily obtaining good cohesive strength and easily obtaining adhesive reliability at high temperatures. The hydroxyl group-containing monomer may be used alone or in combination of two or more kinds.

[0117] [1-3. Nitrogen-containing monomers] The nitrogen atom-containing monomer means a monomer having at least one nitrogen atom in the molecule (per molecule). However, the above-mentioned hydroxyl group-containing monomer does not include the above-mentioned nitrogen atom-containing monomer. That is, in this specification, a monomer having a hydroxyl group and a nitrogen atom in the molecule is included in the nitrogen atom-containing monomer. Also, a monomer having at least one nitrogen atom in the molecule and at least one carboxyl group in the molecule is a carboxyl group-containing monomer, but is not a nitrogen atom-containing monomer.

[0118] As the nitrogen atom-containing monomer, from the viewpoint of improving foaming and peeling resistance, N-vinyl cyclic amide, (meth)acrylamide, etc. are preferable. The nitrogen atom-containing monomer may be used alone or in combination of two or more kinds.

[0119] As the N-vinyl cyclic amide, from the viewpoint of facilitating obtaining good cohesive strength and facilitating obtaining adhesive reliability at high temperatures, the N-vinyl cyclic amide represented by the following formula (1) is preferable. [ka] (In formula (1), R 1 represents a divalent organic group.

[0120] R in the above formula (1) 1 is a divalent organic group, preferably a divalent saturated or unsaturated hydrocarbon group, and more preferably a divalent saturated hydrocarbon group (for example, an alkylene group having 3 to 5 carbon atoms).

[0121] As the N-vinyl cyclic amide represented by the above formula (1), from the viewpoint of further improving foaming and peeling resistance, N-vinyl-2-pyrrolidone (NVP), N-vinyl-2-piperidone, N-vinyl-2-caprolactam, N-vinyl-3-morpholinone, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, etc. are preferred, more preferably N-vinyl-2-pyrrolidone, N-vinyl-2-caprolactam, and even more preferably N-vinyl-2-pyrrolidone.

[0122] Examples of the (meth)acrylamides include (meth)acrylamide, N-alkyl(meth)acrylamide, and N,N-dialkyl(meth)acrylamide. Examples of the N-alkyl(meth)acrylamide include N-ethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, Nn-butyl(meth)acrylamide, and N-octylacrylamide. Furthermore, the N-alkyl(meth)acrylamide also includes (meth)acrylamides having an amino group, such as dimethylaminoethyl(meth)acrylamide, diethylaminoethyl(meth)acrylamide, and dimethylaminopropyl(meth)acrylamide. Examples of the N,N-dialkyl(meth)acrylamide include N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, N,N-di(n-butyl)(meth)acrylamide, and N,N-di(t-butyl)(meth)acrylamide.

[0123] The (meth)acrylamides also include, for example, various N-hydroxyalkyl (meth)acrylamides. Examples of the N-hydroxyalkyl (meth)acrylamides include N-methylol (meth)acrylamide, N-(2-hydroxyethyl) (meth)acrylamide, N-(2-hydroxypropyl) (meth)acrylamide, N-(1-hydroxypropyl) (meth)acrylamide, N-(3-hydroxypropyl) (meth)acrylamide, N-(2-hydroxybutyl) (meth)acrylamide, N-(3-hydroxybutyl) (meth)acrylamide, N-(4-hydroxybutyl) (meth)acrylamide, and N-methyl-N-2-hydroxyethyl (meth)acrylamide.

[0124] The (meth)acrylamides also include, for example, various N-alkoxyalkyl (meth)acrylamides, such as N-methoxymethyl (meth)acrylamide and N-butoxymethyl (meth)acrylamide.

[0125] Examples of nitrogen atom-containing monomers other than the N-vinyl cyclic amides and the (meth)acrylamides include amino group-containing monomers such as aminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, and t-butylaminoethyl (meth)acrylate; cyano group-containing monomers such as acrylonitrile and methacrylonitrile; (meth)acryloylmorpholine, N-vinylpiperazine, N-vinylpyrrole, N-vinylimidazole, N-vinylpyrazine, N-vinylmorpholine, N-vinylpyrazole, vinylpyridine, vinylpyrimidine, vinyloxazole, vinylisoxazole, vinylthiazole, vinylisothiazole, vinylpyridazine, (meth)acryloylpyrrolidone, (meth)acryloylpyrrolidine, (meth)acryloylpiperidine, N- Examples of the monomer include heterocyclic ring-containing monomers such as methylvinylpyrrolidone; maleimide-based monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; itaconimide-based monomers such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-laurylitaconimide, and N-cyclohexylitaconimide; and succinimide-based monomers such as N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyoctamethylenesuccinimide; and isocyanate-based monomers such as 2-(meth)acryloyloxyethylisocyanate.

[0126] [1-4. Other copolymerizable monomers] Examples of copolymerizable monomers in acrylic polymers include, in addition to the above-mentioned nitrogen atom-containing monomers and hydroxyl group-containing monomers, alicyclic structure-containing monomers [e.g., cyclopropyl (meth)acrylate, cyclobutyl (meth)acrylate, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, cyclooctyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, etc.]; epoxy group-containing monomers [e.g., glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, etc.]; (meth)acrylic acid alkoxyalkyl esters [e.g., 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 3-methoxypropyl (meth)acrylate, (meth)acrylate, meth ... 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, 4-ethoxybutyl (meth)acrylate, etc.]; epoxy group-containing monomers [e.g., glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, etc.]; sulfonic acid group-containing monomers [e.g., sodium vinyl sulfonate, etc.]; phosphate group-containing monomers; (meth)acrylic acid esters having aromatic hydrocarbon groups [e.g., phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, etc.]; vinyl esters [e.g., vinyl acetate, vinyl propionate, etc.]; aromatic vinyl compounds [e.g., styrene, vinyl toluene, etc.]; olefins or dienes [e.g., ethylene, propylene, butadiene, isoprene, isobutylene, etc.]; vinyl ethers [e.g., vinyl alkyl ether, etc.]; vinyl chloride, etc.

[0127] [1-5. Hydrogenated polyolefin resin] The acrylic adhesive composition of the present invention is preferably an acrylic adhesive composition containing an acrylic polymer as a main component and a hydrogenated polyolefin resin. The hydrogenated polyolefin resin is a material with a low dielectric constant, and by blending it with the acrylic polymer of the present invention, the dielectric constant is reduced, and in a touch panel to which an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is laminated, a malfunction of a touch operation can be suppressed. In addition, it is also preferable that a highly flexible adhesive layer can be realized without requiring a low molecular weight acrylic polymer, and that even when an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is laminated, the stress with the metal wiring can be sufficiently relaxed to prevent display unevenness. In addition, the hydrogenated polyolefin resin is also excellent in compatibility with the acrylic polymer, and is therefore preferable in that the transparency of the adhesive layer of the present invention can be maintained to a higher degree. The hydrogenated polyolefin resin can be used alone or in combination of two or more kinds.

[0128] Hydrogenated polyolefin resins are preferred because they can realize a highly flexible adhesive layer and can sufficiently relieve stress with the metal wiring and prevent display unevenness even when bonded to an optical component (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film, and therefore exhibit liquid fluidity at 25°C. A hydrogenated polyolefin resin exhibiting liquid fluidity at 25°C means that its viscosity measured at 25°C using a Brookfield viscometer is 10,000 mPa s or less.

[0129] The hydrogenated polyolefin resin is obtained by reducing the carbon-carbon double bonds contained in the polyolefin resin by a hydrogenation reaction. Since the hydrogenated polyolefin resin has a reduced number of carbon-carbon double bonds in the molecule, it is less likely to cause polymerization inhibition, a decrease in the polymerization rate, or a decrease in molecular weight when the acrylic pressure-sensitive adhesive composition of the present invention is cured by UV irradiation, and therefore the adhesive reliability of the acrylic pressure-sensitive adhesive composition of the present invention at high temperatures can be maintained.

[0130] The hydrogenation rate of the hydrogenated polyolefin resin is preferably 90% or more, more preferably 95% or more, and even more preferably 97% or more, from the viewpoint of preventing polymerization inhibition and improving adhesive reliability at high temperatures. The upper limit of the hydrogenation rate is not particularly limited, but is theoretically 100%, and may be 99.9% or less or 99.8% or less in practice. The hydrogenation rate of the hydrogenated polyolefin resin is 1 It can be determined by, for example, quantifying the amount of double bonds remaining in the hydrogenated polyolefin resin by H-NMR measurement.

[0131] The iodine value (Ig / 100g) of the hydrogenated polyolefin resin is preferably 30 or less, more preferably 25 or less, and even more preferably 20 or less, from the viewpoint of preventing polymerization inhibition and improving adhesive reliability at high temperatures. The lower limit of the iodine value is not particularly limited, but may be 0.1 or more, or 0.2 or more. The iodine value is a value measured in accordance with JIS K 0070-1992.

[0132] The number average molecular weight (Mn) of the hydrogenated polyolefin resin is preferably 1000 to 5000 in order to impart appropriate stress relaxation properties and fluidity to the pressure-sensitive adhesive layer and improve compatibility with the acrylic polymer. The number average molecular weight (Mn) is preferably 1000 or more in order to impart appropriate stress relaxation properties and fluidity to the pressure-sensitive adhesive composition, more preferably 1500 or more, and even more preferably 1800 or more. The number average molecular weight (Mn) is preferably 5000 or less in order to improve compatibility with the acrylic polymer and to maintain the transparency of the acrylic pressure-sensitive adhesive composition of the present invention at a higher level, more preferably 4800 or less, and even more preferably 4600 or less.

[0133] The polydispersity (Mw / Mn) of the hydrogenated polyolefin resin is preferably 2.0 or less, more preferably 1.8 or less, in order to provide the pressure-sensitive adhesive layer with appropriate stress relaxation properties and fluidity, improve compatibility with the acrylic polymer, maintain high transparency, and suppress haze. The lower limit of the polydispersity is not particularly limited, but may be 1.0 or 1.1 or more in practical use.

[0134] The number average molecular weight (Mn) and polydispersity (Mw / Mn) of the hydrogenated polyolefin resin are values ​​measured by gel permeation chromatography (GPC) and calculated based on polystyrene standard.

[0135] The hydrogenated polyolefin resin contains a hydrogenated polyolefin. The acrylic pressure-sensitive adhesive composition of the present invention is suitable from the viewpoint of reducing the dielectric constant and suppressing malfunction of a touch operation in a touch panel by containing a hydrogenated polyolefin as the hydrogenated polyolefin resin.

[0136] The hydrogenated polyolefin is a hydrogenated product of a polymer (polyolefin) having a structural unit derived from an olefin. The hydrogenated polyolefin includes hydrogenated products of homopolymers and copolymers of α-olefins such as ethylene, propylene, 1-butene, isobutene, and 1-hexene; diene compounds such as butadiene and isoprene; and aromatic vinyl compounds such as styrene. The hydrogenated polyolefin is preferably a hydrogenated product of homopolymers or copolymers of diene compounds, such as hydrogenated polybutadiene and hydrogenated polyisoprene. The hydrogenated polyolefins can be used alone or in combination of two or more kinds.

[0137] From the viewpoint of reducing the dielectric constant and suppressing malfunctions during touch operations on a touch panel, the hydrogenated polyolefin resin preferably further contains a hydrogenated polyolefin polyol in addition to the hydrogenated polyolefin.

[0138] The hydrogenated polyolefin polyol is a compound in which the end of the hydrogenated polyolefin is modified with a hydroxyl group. The hydrogenated polyolefin polyol is preferably a hydroxyl group modified product of a homopolymer or copolymer of a diene compound, such as hydrogenated polybutadiene polyol, hydrogenated polyisoprene polyol, etc. The hydrogenated polyolefin polyol can be used alone or in combination of two or more kinds.

[0139] As the hydrogenated polyolefin and hydrogenated polyolefin polyol, hydrogenated polybutadiene polyol and hydrogenated polybutadiene polyol are preferred, respectively, in that they can realize a highly flexible adhesive layer and can sufficiently relieve stress with the metal wiring and prevent display unevenness even when an optical component (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is attached.

[0140] The hydrogenated polybutadiene is preferably one represented by the following formula (2), and the hydrogenated polybutadiene polyol is preferably one represented by the following formula (3). [ka] In the above formula, m represents the degree of polymerization of the hydrogenated polybutadiene.

[0141] Commercially available hydrogenated polyolefins and hydrogenated polyolefin polyols can be used. Commercially available hydrogenated polyolefins include those under the trade names "BI-2000" and "BI-3000" (all manufactured by Nippon Soda Co., Ltd.). Commercially available hydrogenated polyolefin polyols include those under the trade names "GI-1000", "GI-2000", and "GI-3000" (all manufactured by Nippon Soda Co., Ltd.) and those under the trade name "EPOL" (manufactured by Idemitsu Kosan Co., Ltd.).

[0142] The content of the hydrogenated polyolefin resin in the acrylic pressure-sensitive adhesive composition is not particularly limited, but from the viewpoint of reducing the dielectric constant and suppressing malfunction of touch operation in a touch panel, it is preferably 5 parts by weight or more, more preferably 10 parts by weight or more, and even more preferably 15 parts by weight or more, based on 100 parts by weight of the acrylic polymer. On the other hand, from the viewpoint of suppressing an increase in haze and ensuring higher transparency, and from the viewpoint of being able to maintain high adhesive strength and adhesive reliability at high temperatures, the content of the hydrogenated polyolefin resin is preferably 40 parts by weight or less, more preferably 35 parts by weight or less, and even more preferably 30 parts by weight or less.

[0143] The content of hydrogenated polyolefin in the acrylic pressure-sensitive adhesive composition is not particularly limited, but from the viewpoint of reducing the dielectric constant and suppressing malfunction of touch operation in a touch panel, it is preferably 0.5 parts by weight or more, more preferably 1 part by weight or more, and even more preferably 1.5 parts by weight or more, based on 100 parts by weight of the acrylic polymer. On the other hand, from the viewpoint of suppressing an increase in haze and ensuring higher transparency, and from the viewpoint of being able to maintain high adhesive strength and adhesive reliability at high temperatures, the content of hydrogenated polyolefin is preferably 20 parts by weight or less, more preferably 15 parts by weight or less, and even more preferably 12 parts by weight or less.

[0144] The content of the hydrogenated polyolefin polyol in the acrylic pressure-sensitive adhesive composition is not particularly limited, but from the viewpoint of reducing the dielectric constant and suppressing malfunction of touch operation in a touch panel, it is preferably 1 part by weight or more, more preferably 3 parts by weight or more, even more preferably 5 parts by weight or more, and may be 10 parts by weight or more, relative to 100 parts by weight of the acrylic polymer. On the other hand, from the viewpoint of suppressing an increase in haze and ensuring higher transparency, and from the viewpoint of being able to highly maintain adhesive strength and adhesive reliability at high temperatures, the content of the hydrogenated polyolefin polyol is preferably 40 parts by weight or less, more preferably 35 parts by weight or less, even more preferably 30 parts by weight or less, and particularly preferably 25 parts by weight or less.

[0145] The weight ratio of the hydrogenated polyolefin content to the hydrogenated polyolefin polyol content in the acrylic pressure-sensitive adhesive composition (hydrogenated polyolefin / hydrogenated polyolefin polyol) is not particularly limited, but is preferably 1 / 99 or more, more preferably 2 / 98 or more, 3 / 98 or more, or may be 4 / 96 or more, from the viewpoint of reducing the dielectric constant and suppressing malfunction of touch operation in a touch panel. In addition, from the viewpoint of suppressing an increase in haze and ensuring higher transparency, the ratio is preferably 90 / 10 or less, more preferably 80 / 20 or less, and even more preferably 70 / 30 or less, and may be 55 / 45 or less, 45 / 55 or less, or 30 / 70 or less.

[0146] [1-6. Multifunctional (meth)acrylate] The acrylic pressure-sensitive adhesive composition of the present invention preferably further contains a polyfunctional (meth)acrylate, which acts as a cross-linking component and makes it easier for the pressure-sensitive adhesive composition to have an appropriate cohesive strength.

[0147] Examples of the polyfunctional (meth)acrylate include hexanediol di(meth)acrylate, butanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, urethane acrylate, etc. The polyfunctional (meth)acrylate may be used alone or in combination of two or more.

[0148] The content (ratio) of the polyfunctional (meth)acrylate is not particularly limited, but from the viewpoint that the adhesive layer has an appropriate cohesive force, it is preferably 0.001 parts by weight or more, more preferably 0.002 parts by weight or more, even more preferably 0.005 parts by weight or more, and may be 0.01 parts by weight or more, relative to 100 parts by weight of the acrylic polymer. In addition, the content (ratio) of the polyfunctional (meth)acrylate is preferably 0.5 parts by weight or less, more preferably 0.4 parts by weight or less, and even more preferably 0.3 parts by weight or less, relative to 100 parts by weight of the acrylic polymer, from the viewpoint that a highly flexible adhesive layer can be realized, and the stress with the metal wiring can be sufficiently relaxed to prevent display unevenness.

[0149] [1-7. Silane coupling agents] The acrylic pressure-sensitive adhesive composition of the present invention preferably further contains a silane coupling agent. When the pressure-sensitive adhesive composition contains a silane coupling agent, it is preferable in that excellent adhesion to glass (particularly excellent adhesion reliability to glass under high temperature and high humidity) can be easily obtained.

[0150] The silane coupling agent is not particularly limited, but may be γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-phenyl-aminopropyltrimethoxysilane, etc. Among them, γ-glycidoxypropyltrimethoxysilane is preferable. Furthermore, the silane coupling agent may be, for example, a commercially available product such as "KBM-403" (manufactured by Shin-Etsu Chemical Co., Ltd.). The silane coupling agent may be used alone or in combination of two or more kinds.

[0151] The content of the silane coupling agent is not particularly limited, but from the viewpoint of improving the adhesive reliability to glass, it is preferably 0.01 to 1 part by weight, more preferably 0.02 to 0.5 parts by weight, based on 100 parts by weight of the acrylic polymer.

[0152] [1-8. Crosslinking agents] As described above, the acrylic pressure-sensitive adhesive composition of the present invention is preferably not a solvent-based composition, that is, it is preferable that the composition does not contain or substantially does not contain a crosslinking agent. Examples of the crosslinking agent include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, melamine-based crosslinking agents, peroxide-based crosslinking agents, as well as urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, carbodiimide-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, amine-based crosslinking agents, etc. In particular, the acrylic pressure-sensitive adhesive composition of the present invention preferably does not contain or substantially does not contain an isocyanate-based crosslinking agent and / or an epoxy-based crosslinking agent as a crosslinking agent, and preferably does not contain or substantially does not contain an isocyanate-based crosslinking agent.

[0153] Examples of the isocyanate-based crosslinking agent (polyfunctional isocyanate compound) include lower aliphatic polyisocyanates such as 1,2-ethylene diisocyanate, 1,4-butylene diisocyanate, and 1,6-hexamethylene diisocyanate; alicyclic polyisocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, hydrogenated tolylene diisocyanate, and hydrogenated xylene diisocyanate; and aromatic polyisocyanates such as 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate. Examples of the isocyanate crosslinking agent include commercially available products such as trimethylolpropane / tolylene diisocyanate adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate L"), trimethylolpropane / hexamethylene diisocyanate adduct (manufactured by Nippon Polyurethane Industry Co., Ltd., product name "Coronate HL"), and trimethylolpropane / xylylene diisocyanate adduct (manufactured by Mitsui Chemicals, Inc., product name "Takenate D-110N"), etc.

[0154] Examples of the epoxy crosslinking agent (polyfunctional epoxy compound) include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidylaniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitol polyglyceryl diglycidyl ether, and butyl glycol diglycidyl ether. Examples of the epoxy crosslinking agent include glycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, o-phthalic acid diglycidyl ester, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, and epoxy resins having two or more epoxy groups in the molecule. Examples of the epoxy crosslinking agent include commercially available products such as "Tetrad C" manufactured by Mitsubishi Gas Chemical Co., Ltd.

[0155] In the acrylic adhesive composition of the present invention, "substantially does not contain" a crosslinking agent means that the crosslinking agent is not actively mixed in, except when the crosslinking agent is inevitably mixed in. Specifically, a crosslinking agent content in the adhesive composition of 1.0% by weight or less (preferably 0.5% by weight or less, more preferably 0.2% by weight or less) relative to the total amount of the adhesive composition (total weight, 100% by weight) can be said to be substantially not contained. In addition, a crosslinking agent content of preferably 0.05 parts by weight or less (e.g., 0 to 0.05 parts by weight), more preferably 0.01 parts by weight or less (e.g., 0 to 0.01 parts by weight), and even more preferably 0.001 parts by weight or less (e.g., 0 to 0.001 parts by weight) relative to the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer can also be said to be substantially not contained.

[0156] [1-9. Additives] The acrylic adhesive composition of the present invention may contain known additives such as crosslinking accelerators, tackifier resins (rosin derivatives, polyterpene resins, oil-soluble phenols, etc.), antioxidants, fillers, colorants (pigments, dyes, etc.), UV absorbers, chain transfer agents, plasticizers, softeners, surfactants, antistatic agents, rust inhibitors, and antioxidants, as long as the properties of the present invention are not impaired. From the viewpoint of suppressing an increase in haze of the adhesive layer of the present invention, it is preferable that the acrylic adhesive composition of the present invention is substantially free of rust inhibitors and antioxidants. Such additives may be used alone or in combination of two or more.

[0157] From the viewpoint of suppressing an increase in haze of the pressure-sensitive adhesive layer of the present invention, it is preferable that the acrylic pressure-sensitive adhesive composition of the present invention does not substantially contain an antioxidant. "Substantially does not contain" an antioxidant means that the antioxidant is not actively blended, except when the antioxidant is inevitably mixed in. Specifically, a pressure-sensitive adhesive composition having an antioxidant content of 1.0% by weight or less (preferably 0.5% by weight or less, more preferably 0.2% by weight or less) relative to the total amount of the pressure-sensitive adhesive composition (total weight, 100% by weight) can be said to be substantially free of antioxidant. In addition, a pressure-sensitive adhesive composition having an antioxidant content of, for example, 0.5 parts by weight or less (e.g., 0 to 0.5 parts by weight), 0.05 parts by weight or less (e.g., 0 to 0.05 parts by weight), more preferably 0.01 parts by weight or less (e.g., 0 to 0.01 parts by weight), and even more preferably 0.001 parts by weight or less (e.g., 0 to 0.001 parts by weight) relative to the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer can also be said to be substantially free of antioxidant.

[0158] [1-10. Preparation of acrylic adhesive composition] The acrylic adhesive composition of the present invention can be prepared by mixing an acrylic polymer, and if necessary, a hydrogenated polyolefin resin, a polyfunctional (meth)acrylate, a silane coupling agent, and other additives, and stirring them uniformly. At that time, a monomer component constituting an acrylic polymer may be blended from the viewpoint of adjusting the elastic modulus of the adhesive layer. When a monomer component constituting an acrylic polymer is used for adjusting the elastic modulus, it is preferable to prepare the acrylic polymer from a monomer mixture excluding the monomer component used, in order to maintain the above-mentioned properties of the adhesive layer. The monomer component used for adjusting the elastic modulus is not particularly limited, but for example, the functional group-containing monomer described above is preferable, and the hydroxyl group-containing monomer described above is more preferable.

[0159] The amount of the monomer component used to adjust the elastic modulus is not particularly limited, but from the viewpoint of appropriately adjusting the elastic modulus of the pressure-sensitive adhesive layer, it is preferably 5 to 30 parts by weight, and more preferably 10 to 20 parts by weight, per 100 parts by weight of all monomer units of the acrylic polymer (total amount of monomer components constituting the acrylic polymer).

[0160] [2. Adhesive sheet] The pressure-sensitive adhesive sheet of the present invention is not particularly limited as long as it has the pressure-sensitive adhesive layer of the present invention (particularly, a pressure-sensitive adhesive layer formed from the acrylic pressure-sensitive adhesive composition of the present invention).

[0161] The pressure-sensitive adhesive sheet of the present invention may be a double-sided pressure-sensitive adhesive sheet in which both sides are pressure-sensitive adhesive layer surfaces, or a single-sided pressure-sensitive adhesive sheet in which only one side is a pressure-sensitive adhesive layer surface. In particular, from the viewpoint of bonding two members together, a double-sided pressure-sensitive adhesive sheet is preferable. In this specification, the term "pressure-sensitive adhesive sheet" also includes a tape-like one, i.e., an "adhesive tape". In this specification, the pressure-sensitive adhesive layer surface may be referred to as the "adhesive surface".

[0162] The pressure-sensitive adhesive sheet of the present invention may have a release liner provided on the pressure-sensitive adhesive surface until use.

[0163] The pressure-sensitive adhesive sheet of the present invention may be a so-called "substrate-less type" pressure-sensitive adhesive sheet that does not have a substrate (substrate layer) (hereinafter, may be referred to as a "substrate-less pressure-sensitive adhesive sheet"), or may be a type of pressure-sensitive adhesive sheet that has a substrate (hereinafter, may be referred to as a "substrate-attached pressure-sensitive adhesive sheet"). Examples of the substrate-less pressure-sensitive adhesive sheet include a double-sided pressure-sensitive adhesive sheet consisting of only the pressure-sensitive adhesive layer, and a double-sided pressure-sensitive adhesive sheet consisting of the pressure-sensitive adhesive layer and a pressure-sensitive adhesive layer other than the pressure-sensitive adhesive layer (hereinafter, may be referred to as an "other pressure-sensitive adhesive layer"). On the other hand, examples of the substrate-attached pressure-sensitive adhesive sheet include a pressure-sensitive adhesive sheet having the pressure-sensitive adhesive layer on at least one side of the substrate. Among these, a substrate-less pressure-sensitive adhesive sheet (substrate-less double-sided pressure-sensitive adhesive sheet) is preferred, and a substrate-less double-sided pressure-sensitive adhesive sheet consisting of only the pressure-sensitive adhesive layer is more preferred. The "substrate (substrate layer)" does not include a release liner that is peeled off when the pressure-sensitive adhesive sheet is used (applied).

[0164] 1 is a schematic diagram (cross-sectional view) showing a specific example of a preferred embodiment of the pressure-sensitive adhesive sheet of the present invention, in which 1 indicates a pressure-sensitive adhesive sheet, 10 indicates a pressure-sensitive adhesive layer of the present invention, and 11 and 12 indicate release liners. In Fig. 1, the pressure-sensitive adhesive sheet 1 is a substrate-less double-sided pressure-sensitive adhesive sheet, and the adhesive surfaces on both sides of the pressure-sensitive adhesive layer 10 are protected by release liners 11 and 12. Since the adhesive layer 10 is composed of the adhesive layer of the present invention, the adhesive sheet 1 is highly reliable in that its adhesive strength is resistant to changes in the environment, and changes in adhesive strength due to the storage environment immediately after film formation are small, resulting in excellent productivity.

[0165] The thickness (total thickness) of the pressure-sensitive adhesive sheet of the present invention is not particularly limited, but is preferably 12 to 350 μm, and more preferably 12 to 300 μm. If the thickness is at least a certain level, in a touch panel to which an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is attached, the stress with the metal wiring can be sufficiently alleviated to prevent display unevenness, which is preferable. In addition, if the thickness is less than a certain level, it is preferable in that an excellent appearance is easily maintained during production and roll storage, and glue stains are unlikely to occur during cutting processing. Note that the thickness of the pressure-sensitive adhesive sheet of the present invention does not include the thickness of the release liner.

[0166] The haze (according to JIS K7136) of the pressure-sensitive adhesive sheet of the present invention is not particularly limited, but is preferably 1.0% or less, more preferably 0.8% or less. When the haze is 1.0% or less, excellent transparency and excellent appearance can be obtained, which is preferable. The lower limit of the haze is not particularly limited, but is theoretically 0%, and may be more than 0.01% in practical use. The haze can be measured, for example, by leaving the pressure-sensitive adhesive sheet at room temperature (23°C, 50% RH) for at least 24 hours, peeling off a release liner if one is present, and attaching the sheet to a slide glass (for example, one with a total light transmittance of 92% and a haze of 0.2%) as a sample, using a haze meter (manufactured by Murakami Color Research Laboratory Co., Ltd., product name "HM-150N") or an equivalent product.

[0167] The total light transmittance (according to JIS K7361-1) in the visible light wavelength region of the pressure-sensitive adhesive sheet of the present invention is not particularly limited, but is preferably 90% or more, more preferably 91% or more, and even more preferably 92% or more. If the total light transmittance is 90% or more, excellent transparency and excellent appearance can be obtained, which is preferable. The upper limit of the total light transmittance is not particularly limited, but theoretically, it is a value obtained by subtracting the light loss (Fresnel loss) due to reflection at the air interface from 100%, and in practical use, it may be 95% or less. The total light transmittance can be measured, for example, by leaving the pressure-sensitive adhesive sheet at normal conditions (23°C, 50% RH) for at least 24 hours, peeling off the release liner if it has one, and bonding it to a slide glass (for example, one with a total light transmittance of 92% and a haze of 0.2%) as a sample, using a haze meter (manufactured by Murakami Color Research Laboratory Co., Ltd., product name "HM-150N") or an equivalent.

[0168] The pressure-sensitive adhesive sheet of the present invention is not particularly limited, but is preferably manufactured according to a known or conventional manufacturing method. For example, when the pressure-sensitive adhesive sheet of the present invention is a substrate-less pressure-sensitive adhesive sheet, it is obtained by forming the pressure-sensitive adhesive layer on a release liner by the above-mentioned method. When the pressure-sensitive adhesive sheet of the present invention is a substrate-attached pressure-sensitive adhesive sheet, it may be obtained by directly forming the pressure-sensitive adhesive layer on the surface of the substrate (direct transfer method), or it may be obtained by forming the pressure-sensitive adhesive layer on a release liner once, and then transferring (attaching) it to the substrate, thereby providing the pressure-sensitive adhesive layer on the substrate (transfer method).

[0169] The pressure-sensitive adhesive sheet of the present invention may have other layers in addition to the pressure-sensitive adhesive layer. Examples of the other layers include other pressure-sensitive adhesive layers (pressure-sensitive adhesive layers other than the pressure-sensitive adhesive layer of the present invention), intermediate layers, undercoat layers, etc. The pressure-sensitive adhesive sheet of the present invention may have two or more other layers.

[0170] When the pressure-sensitive adhesive sheet of the present invention is a pressure-sensitive adhesive sheet with a substrate, the substrate is not particularly limited, and examples thereof include various optical films such as plastic films, anti-reflection (AR) films, polarizing plates, and retardation plates. Examples of materials for the plastic films and the like include polyester resins such as polyethylene terephthalate (PET), acrylic resins such as polymethyl methacrylate (PMMA), polycarbonate, triacetyl cellulose (TAC), polysulfone, polyarylate, polyimide, polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, ethylene-propylene copolymers, and cyclic olefin polymers such as trade names "Arton (cyclic olefin polymer, manufactured by JSR Corporation)" and "ZEONOR (cyclic olefin polymer, manufactured by Zeon Corporation)". These plastic materials may be used alone or in combination of two or more kinds. In addition, the above-mentioned "substrate" refers to a portion that is attached to the adherend together with the pressure-sensitive adhesive layer when the pressure-sensitive adhesive sheet is attached to the adherend. The release liner that is peeled off when the pressure-sensitive adhesive sheet is used (attached) is not included in the "substrate".

[0171] The substrate is preferably transparent. The total light transmittance (according to JIS K7361-1) of the substrate in the visible light wavelength region is not particularly limited, but is preferably 85% or more, more preferably 88% or more. The haze (according to JIS K7136) of the substrate is not particularly limited, but is preferably 1.0% or less, more preferably 0.8% or less. Examples of such transparent substrates include PET films and non-oriented films such as those under the trade names "Arton" and "Zeonor".

[0172] The thickness of the substrate is not particularly limited, but is preferably, for example, 12 to 500 μm. The substrate may have either a single layer or a multi-layer structure. The surface of the substrate may be appropriately subjected to a known and commonly used surface treatment, such as a physical treatment such as a corona discharge treatment or a plasma treatment, or a chemical treatment such as an undercoat treatment.

[0173] The pressure-sensitive adhesive sheet of the present invention may have a release liner on the adhesive surface until use. When the pressure-sensitive adhesive sheet of the present invention is a double-sided pressure-sensitive adhesive sheet, each adhesive surface may be protected by two release liners, or may be protected by a single release liner having release surfaces on both sides in a rolled form. The release liner is used as a protective material for the pressure-sensitive adhesive layer, and is peeled off when the pressure-sensitive adhesive sheet is attached to an adherend. When the pressure-sensitive adhesive sheet of the present invention is a substrateless pressure-sensitive adhesive sheet, the release liner also serves as a support for the pressure-sensitive adhesive layer. The release liner may not necessarily be provided.

[0174] The release liner is not particularly limited, but examples thereof include a release liner having a release layer (release treatment layer) on at least one surface of the release liner substrate, a low-adhesion release liner made of a fluorine-based polymer, and a low-adhesion release liner made of a non-polar polymer. The fluorine-based polymer is not particularly limited, but examples thereof include polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, and chlorofluoroethylene-vinylidene fluoride copolymer. The non-polar polymer is not particularly limited, but examples thereof include olefin resins such as polyethylene (PE) and polypropylene (PP). Among them, it is preferable to use a release liner having a release layer on at least one surface of the release liner substrate.

[0175] The release liner substrate is not particularly limited, but may include plastic films. Examples of such plastic films include plastic films made of polyester resins such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), and polybutylene terephthalate (PBT); olefin resins containing α-olefin as a monomer component, such as polyethylene (PE), polypropylene (PP), polymethylpentene (PMP), ethylene-propylene copolymer, and ethylene-vinyl acetate copolymer (EVA); polyvinyl chloride (PVC); vinyl acetate resins; polycarbonate (PC); polyphenylene sulfide (PPS); amide resins such as polyamide (nylon) and fully aromatic polyamide (aramid); polyimide resins; and polyether ether ketone (PEEK). Among these, plastic films made of polyester resins are preferred from the viewpoints of processability, availability, workability, dust resistance, cost, and the like, and PET films are more preferred.

[0176] The release agent constituting the release layer is not particularly limited, but examples thereof include silicone-based release agents, fluorine-based release agents, long-chain alkyl-based release agents, molybdenum sulfide, and other release agents. Among them, silicone-based release agents are preferred from the viewpoint of release control and stability over time. The release agents can be used alone or in combination of two or more.

[0177] The release layer may be a single layer, or may have a laminated structure in which two or more layers are laminated, provided that the characteristics of the present invention are not impaired.

[0178] Among these, a preferred specific configuration of the release liner is one in which a PET film is used as the release liner substrate, and a release layer made of a silicone-based release treatment agent is provided on at least one surface of the release liner substrate. Of the two surfaces of the release liner, the surface opposite the side in contact with the pressure-sensitive adhesive layer and on which no release layer is provided is sometimes referred to as the "back surface" of the release liner.

[0179] The release liner may have a carrier material laminated on the back surface in order to ensure punching processability and handling property, and to increase the thickness while maintaining flexibility. Such a carrier material is not particularly limited, but examples thereof include a structure in which a PET film substrate is laminated in two layers via an adhesive layer, and a structure in which a COP film substrate and a PET film substrate are laminated in two layers via an adhesive layer. The release liner may not have a carrier material.

[0180] The release liner may have a conductive treatment layer on the release layer and / or back surface in order to suppress electrostatic charge that occurs during transportation or when the release liner is peeled off, and to reduce adhesion or inclusion of foreign matter. Such a conductive treatment layer is not particularly limited, but examples thereof include a coating treatment layer mainly composed of a composite of poly(3,4-ethylenedioxythiophene) (PEDOT) and polystyrene sulfonate (PSS) as a conductive polymer. The release liner does not have to have a conductive treatment layer.

[0181] The release liner can be manufactured by a known method. The carrier material and conductive treatment layer can be prepared by laminating them on the release layer and / or back surface of the release liner by a known method. The release liner of the present invention may also have other layers (e.g., an intermediate layer, an undercoat layer, etc.) within the scope of not impairing the effects of the present invention.

[0182] The thickness of the release liner is not particularly limited, but from the standpoint of cost and ease of handling of the pressure-sensitive adhesive sheet during lamination, it is preferably 12 to 200 μm, more preferably 25 to 150 μm, and even more preferably 38 to 125 μm.

[0183] Furthermore, when the pressure-sensitive adhesive sheet of the present invention is a double-sided pressure-sensitive adhesive sheet of the double release liner type, a release liner is provided on one adhesive surface, and a release liner is also provided on the other adhesive surface. In such a case, it is preferable that both release liners are release liners in which only one surface of each is a release layer (particularly a release liner in which one surface of a plastic substrate has a release layer made of a silicone-based release agent). Furthermore, the release liner is provided so that the release layer is in contact with the adhesive surface.

[0184] Furthermore, when the pressure-sensitive adhesive sheet of the present invention is a double-sided pressure-sensitive adhesive sheet of double release liner type, it is preferable that there is a difference in the release strength of the two release liners. For example, when the pressure-sensitive adhesive sheet of the present invention is a double-sided pressure-sensitive adhesive sheet of double release liner type, it is preferable that one release liner is used for the adhesive surface (also called "first surface side") that is used (applied) first, and the other release liner is used for the adhesive surface (also called "second surface side") that is used (applied) later. Therefore, it is preferable that one release liner is used as a release liner of the "light release side" that can be peeled off with a smaller force (peeling force), and the other release liner is used as a release liner of the "heavy release side" that requires a larger force (peeling force) to peel off from the pressure-sensitive adhesive layer. In this specification, the release liner of the light release side may be referred to as a "light release liner", and the release liner of the heavy release surface may be referred to as a "heavy release liner".

[0185] When the pressure-sensitive adhesive sheet of the present invention is a double-sided pressure-sensitive adhesive sheet of a single release liner type, a release liner is provided on one adhesive surface, and by rolling this, the other adhesive surface of the adhesive body is also protected by the release liner. When the pressure-sensitive adhesive sheet of the present invention is a single release liner type, it is preferable that both surfaces of the release liner are release layers (release treatment layers). Of the two release layers of the release liner, the release layer on the side that comes into contact with the adhesive surface by rolling is sometimes referred to as the "back release layer". Usually, the back release layer side of the release liner is used for the "one side" of the double-sided pressure-sensitive adhesive sheet.

[0186] The pressure-sensitive adhesive layer of the present invention is provided with stress relaxation properties, which is preferable in that it suppresses roughening or deformation of the adhesive surface of the pressure-sensitive adhesive layer and the occurrence of stick-slip when the release liner is peeled off, thereby enabling the pressure-sensitive adhesive sheet to be used stably. Stick-slip is a vibration phenomenon that occurs on the peeling surface, which can damage and break the adherend or leave adhesive residue partially on the adherend.

[0187] When the pressure-sensitive adhesive sheet of the present invention is a double-sided pressure-sensitive adhesive sheet, in order to suppress roughening or deformation of the adhesive surface of the pressure-sensitive adhesive layer and the occurrence of stick-slip when the release liner is peeled off and to enable the pressure-sensitive adhesive sheet to be used stably, the release force (release liner release force) from one side (light release side) of the release liner to the pressure-sensitive adhesive layer is 0.01 to 0.5 N / 50 mm, preferably 0.05 to 0.25 N / 50 mm, and the release force (release liner release force) from the second side (heavy release side) of the release liner to the pressure-sensitive adhesive layer (e.g., the acrylic pressure-sensitive adhesive layer, the rubber-based pressure-sensitive adhesive layer, etc.) is 0.1 to 1.00 N / 50 mm, preferably 0.2 to 0.85 N / 50 mm, and it is preferable that the release liner release force on the heavy release side is always greater than the release liner release force on the light release side, with a release difference of about 1.1 to 10.0 times.

[0188] In particular, when the pressure-sensitive adhesive sheet of the present invention is a double-sided pressure-sensitive adhesive sheet, in order to suppress the so-called weeping phenomenon, roughening or deformation of the adhesive surface of the pressure-sensitive adhesive layer when the release liner is peeled off, and stick-slip, and to enable stable use of the pressure-sensitive adhesive sheet, it is preferable that the difference between the peel force of the heavy release liner to the pressure-sensitive adhesive layer (release liner peel force) and the peel force of the light release liner to the pressure-sensitive adhesive layer (release liner peel force) be 0.01 N / 50 mm or more, more preferably 0.02 N / 50 mm or more, even more preferably 0.05 N / 50 mm or more, and particularly preferably 0.06 N / 50 mm or more.

[0189] The release strength of the release liner means the 180° peel adhesive strength of the release liner to the adhesive layer measured by a 180° peel test, where the pulling speed is 300 mm / min.

[0190] The pressure-sensitive adhesive sheet of the present invention has the pressure-sensitive adhesive layer of the present invention (particularly, the pressure-sensitive adhesive layer formed by the acrylic pressure-sensitive adhesive composition of the present invention), and therefore has high reliability in that the adhesive strength is unlikely to change with environmental changes, and the change in adhesive strength due to the storage environment immediately after film formation is small, resulting in excellent productivity. In addition, it has excellent flexibility, and even when an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is attached, it can prevent display unevenness of a display device or an input device. Furthermore, it has excellent adhesion, foaming peel resistance, and step followability.

[0191] Therefore, the pressure-sensitive adhesive sheet of the present invention is useful for adhering optical members such as polarizing films, retardation films, optical compensation films, touch sensor films, and cover films to image display panels in image display devices and touch panels incorporating touch sensors in these image display devices, or for adhering these optical members to each other. The pressure-sensitive adhesive sheet of the present invention is also useful for adherends that are prone to foaming at the interface at high temperatures. For example, polymethyl methacrylate resin (PMMA) may contain unreacted monomers, and is prone to foaming due to foreign matter at high temperatures. Polycarbonate (PC) is also prone to outgassing of water and carbon dioxide at high temperatures. The pressure-sensitive adhesive sheet of the present invention is excellent in resistance to foaming and peeling, and is therefore useful for adherends containing such resins.

[0192] The pressure-sensitive adhesive sheet of the present invention is useful not only for adherends with a small linear expansion coefficient, but also for adherends with a large linear expansion coefficient. The adherend with a small linear expansion coefficient is not particularly limited, but may be, for example, a glass plate (linear expansion coefficient: 0.3×10 -5 ~0.8×10 -5 / ℃), polyethylene terephthalate substrate (PET film, linear expansion coefficient: 1.5×10 -5 ~2×10 -5 The adherend having a large linear expansion coefficient is not particularly limited, but may be, for example, a resin substrate having a large linear expansion coefficient. More specifically, a polycarbonate resin substrate (PC, linear expansion coefficient: 7×10 -5 ~8×10 -5 / ℃), polymethyl methacrylate resin base material (PMMA, linear expansion coefficient: 7×10 -5 ~8×10 -5 / ℃), cycloolefin polymer substrate (COP, linear expansion coefficient: 6×10 -5 ~7×10 -5 / ° C.), trade name "ZEONOR" (manufactured by Zeon Corporation), trade name "ARTON" (manufactured by JSR Corporation), and the like.

[0193] The pressure-sensitive adhesive sheet of the present invention is useful for bonding an adherend having a small linear expansion coefficient to an adherend having a large linear expansion coefficient. Specifically, the pressure-sensitive adhesive sheet of the present invention is preferably used for bonding a glass adherend (e.g., a glass plate, chemically strengthened glass, a glass lens, etc.) to the resin substrate having a large linear expansion coefficient.

[0194] Thus, the pressure-sensitive adhesive sheet of the present invention is useful for bonding adherends made of various materials together, and is particularly useful for bonding glass adherends to plastic adherends.

[0195] Furthermore, the pressure-sensitive adhesive sheet of the present invention is useful not only for adherends with a smooth surface, but also for adherends with steps on the surface, such as optical members (touch sensor films) having metal wiring such as metal mesh films and silver nanowire films. In particular, the pressure-sensitive adhesive sheet of the present invention is useful for bonding a glass adherend to the resin substrate having a large linear expansion coefficient, even if at least one of the glass adherend and the resin substrate having a large linear expansion coefficient has steps on the surface.

[0196] The pressure-sensitive adhesive sheet of the present invention is preferably used in the manufacture of portable electronic devices, such as mobile phones, PHS, smartphones, tablets (tablet computers), mobile computers (mobile PCs), personal digital assistants (PDAs), electronic organizers, portable broadcast receivers such as portable televisions and portable radios, portable game consoles, portable audio players, portable DVD players, cameras such as digital cameras, and camcorder-type video cameras.

[0197] The pressure-sensitive adhesive sheet of the present invention is preferably used, for example, for bonding members or modules constituting a portable electronic device to each other, or for fixing members or modules constituting a portable electronic device to a housing. More specifically, examples of the adhesive sheet include bonding a cover glass or lens (particularly a glass lens) to a touch panel or a touch sensor film (particularly a touch sensor film having metal wiring such as a metal mesh film or a silver nanowire film), bonding a polarizing film to a touch panel or a touch sensor, bonding a display panel to a touch panel or a touch sensor film, fixing a cover glass or lens (particularly a glass lens) to a housing, fixing a display panel to a housing, fixing an input device such as a sheet-like keyboard or a touch panel to a housing, bonding a protective panel of an information display unit to a housing, bonding housings together, bonding a housing to a decorative sheet, and fixing or bonding various members and modules constituting a portable electronic device. In this specification, the display panel refers to a structure at least composed of a lens (particularly a glass lens) and a touch panel. In addition, the lens in this specification is a concept that includes both a transparent body that exhibits a light refraction action and a transparent body that does not have a light refraction action. In other words, the lens in this specification also includes a simple window panel that has no refractive effect.

[0198] Furthermore, the pressure-sensitive adhesive sheet of the present invention is preferably used for optical applications. That is, the pressure-sensitive adhesive sheet of the present invention is preferably an optical pressure-sensitive adhesive sheet used for optical applications. More specifically, it is preferably used for, for example, bonding optical members (for bonding optical members) or for manufacturing products (optical products) using the optical members.

[0199] [3. Optical components with pressure-sensitive adhesive layers, image display devices, touch panels] The pressure-sensitive adhesive layer-attached optical member of the present invention is not particularly limited as long as it is an optical member having a pressure-sensitive adhesive layer in which the pressure-sensitive adhesive sheet of the present invention is attached to at least one side of the optical member. The pressure-sensitive adhesive layer of the pressure-sensitive adhesive layer-attached optical member of the present invention may have a release liner on the adhesive surface until use, but may not have a release liner. The pressure-sensitive adhesive layer-attached optical member of the present invention is formed by adhering the pressure-sensitive adhesive sheet of the present invention, and therefore has high reliability in that the adhesive strength is unlikely to change with environmental changes, and the adhesive strength does not change much due to the storage environment immediately after film formation, and is excellent in productivity. In addition, the optical member has high flexibility, can sufficiently relieve stress with the metal wiring, can prevent display unevenness, and has excellent adhesion reliability, particularly at high temperatures.

[0200] The pressure-sensitive adhesive layer-attached optical member of the present invention may be one in which the pressure-sensitive adhesive sheet of the present invention is attached to an optical member (touch sensor film) having metal wiring such as a metal mesh film, a silver nanowire film, etc. In this case, it is preferable that the pressure-sensitive adhesive sheet of the present invention is attached to the surface of the touch sensor film on the side having the metal wiring.

[0201] FIG. 2 is a schematic diagram (cross-sectional view) showing a specific example of a preferred embodiment of the pressure-sensitive adhesive layer-attached optical member of the present invention. In Figure 2(a), 2A is an optical member with an adhesive layer, 20 is the adhesive layer of the present invention, 21 is an optical member, and 22 is a release liner, with the adhesive layer 20 laminated on one side of the optical member 21, and the adhesive surface of the adhesive layer 20 opposite the optical member 21 being protected by the release liner 22. In Figure 2(b), 2B is an optical component with an adhesive layer (touch sensor film with an adhesive layer), 20 is the adhesive layer of the present invention, 23 is the touch sensor film, 22 is a release liner, and 24 is the metal wiring, with the adhesive layer 20 laminated on the surface of the touch sensor film 23 on which the metal wiring 24 is formed, and the adhesive surface of the adhesive layer 20 opposite the touch sensor film 23 is protected by a release liner 22. Since the adhesive layer 20 is composed of the adhesive layer of the present invention, the optical member 2A with an adhesive layer and the touch sensor film 2B with an adhesive layer are highly reliable in that their adhesive strength is resistant to changes in the environment, and changes in adhesive strength due to the storage environment immediately after film formation are small, resulting in excellent productivity.

[0202] From the viewpoint of obtaining a further excellent corrosion prevention effect, it is further preferable that the pressure-sensitive adhesive layer-attached optical member further has a pressure-sensitive adhesive layer attached to the surface of the optical member opposite to the surface having the pressure-sensitive adhesive layer. The pressure-sensitive adhesive layer is preferably the pressure-sensitive adhesive layer of the present invention.

[0203] The material constituting the metal wiring is not particularly limited, and examples thereof include metals such as titanium, silicon, niobium, indium, zinc, tin, gold, silver, copper, aluminum, cobalt, chromium, nickel, lead, iron, palladium, platinum, tungsten, zirconium, tantalum, and hafnium. Furthermore, materials containing two or more of these metals and alloys mainly composed of these metals are also included. Among them, gold, silver, and copper are preferred from the viewpoint of electrical conductivity, and silver and copper are more preferred from the viewpoint of electrical conductivity and cost. That is, the metal wiring is preferably silver wiring and / or copper wiring, particularly copper mesh wiring, silver mesh wiring, and silver nanowires. In addition, an oxide film or a metal coating film may be provided on the metal wiring for the purpose of higher rust prevention.

[0204] An optical member refers to a member having optical properties (for example, polarization, light refraction, light scattering, light reflectivity, light transmittance, light absorption, light diffraction, optical rotation, visibility, etc.). The substrate constituting the optical member is not particularly limited, but examples thereof include substrates constituting devices (optical devices) such as image display devices and touch panels, or substrates used in these devices, such as polarizing films, wave plates, retardation films, optical compensation films, brightness-enhancing films, light guide plates, reflective films, anti-reflection films, hard-coated films (films in which at least one side of a plastic film such as a PET film has been subjected to a hard-coat treatment), transparent conductive films (for example, plastic films having an ITO layer on the surface (preferably, ITO films such as PET-ITO, polycarbonate, and cycloolefin polymer), etc.), design films, decorative films, surface protection plates, prisms, lenses, color filters, transparent substrates (glass substrates such as glass sensors, glass display panels (LCDs, etc.), and glass substrates such as glass plates with transparent electrodes), and substrates on which these are laminated (these may be collectively referred to as "functional films"). These films may also have metal wiring such as a metal nanowire layer or a conductive polymer layer. These films may also have metal thin wires printed in a mesh pattern. The above terms "plate" and "film" each include plate-like, film-like, sheet-like, and other shapes, and for example, "polarizing film" includes "polarizing plate" and "polarizing sheet", etc. Furthermore, "film" includes film sensors, etc.

[0205] In particular, the pressure-sensitive adhesive sheet of the present invention can be suitably used for transparent conductive films (metal mesh films, silver nanowire films) in which the metal wiring is metal mesh wiring or silver nanowires, particularly optical members (touch sensor films) having metal mesh films. When an optical member having metal wiring such as a metal mesh film or a silver nanowire film is bonded via a pressure-sensitive adhesive sheet, there is a problem that display unevenness is likely to occur in the peripheral portion of the image display panel due to stress distortion or the like applied to the pressure-sensitive adhesive around the metal wiring. Therefore, the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet to which an optical member having metal wiring is bonded is required to have flexibility to relieve the stress with the metal wiring in order to prevent display unevenness.

[0206] In the pressure-sensitive adhesive sheet of the present invention, the pressure-sensitive adhesive layer of the present invention is highly flexible, and even when a film having metal wiring such as a metal mesh film or a silver nanowire film is laminated, the stress with the metal wiring can be sufficiently relaxed to prevent display unevenness. In addition, an image display device or a touch panel having the pressure-sensitive adhesive sheet of the present invention has excellent durability because an optical member is laminated by a highly reliable pressure-sensitive adhesive layer whose adhesive strength is unlikely to change due to environmental changes.

[0207] Examples of the image display device include a liquid crystal display device, an organic EL (electroluminescence) display device, a PDP (plasma display panel), and electronic paper.

[0208] The substrate constituting the optical member is not particularly limited, and examples thereof include substrates (e.g., sheet-shaped, film-shaped, or plate-shaped substrates) made of glass, acrylic resin, polycarbonate, polyethylene terephthalate, cycloolefin polymer, metal thin film, etc. As described above, the "optical member" in the present invention also includes members (design films, decorative films, surface protection films, etc.) that play a role in decorating or protecting an image display device or a touch panel while maintaining its visibility.

[0209] If the adhesive sheet of the present invention is an adhesive sheet with a substrate and the adhesive sheet constitutes a member having optical properties, the substrate can be regarded as the same as the substrate, and the adhesive sheet can also be said to be an adhesive layer optical member of the present invention.

[0210] When the pressure-sensitive adhesive sheet of the present invention is a pressure-sensitive adhesive sheet with a substrate and the functional film is used as the substrate, the pressure-sensitive adhesive sheet of the present invention can also be used as an "adhesive-type functional film" having the pressure-sensitive adhesive layer on at least one side of the functional film.

[0211] FIG. 3 is a schematic diagram (cross-sectional view) showing a specific example of a preferred embodiment of the image display device of the present invention. In Figure 3, 3 indicates an image display device, 30, 31, and 32 indicate adhesive layers, 33 indicates an image display panel, 34 and 35 indicate polarizing films, and 36 indicates a transparent substrate. The image display device 3 has a polarizing film 35, an adhesive layer 32, an image display panel 33, an adhesive layer 31, a polarizing film 34, an adhesive layer 30, and a transparent substrate 36 laminated in this order.

[0212] At least one of the pressure-sensitive adhesive layers 30, 31, and 32 is composed of the pressure-sensitive adhesive layer of the present invention. Since the image display device 3 includes the pressure-sensitive adhesive layer of the present invention in its laminated structure, the image display device 3 has high reliability in that the adhesive strength is unlikely to change due to environmental changes, and has excellent durability.

[0213] In the image display device 3, the pressure-sensitive adhesive layer 30 is located on the most visible side of the laminated structure, and is most susceptible to the effects of the external environment such as the temperature of the outside air, humidity, and external light. Therefore, the pressure-sensitive adhesive layer 30 is preferably composed of the pressure-sensitive adhesive layer of the present invention, which is highly reliable and has excellent durability and whose adhesive strength is unlikely to change due to environmental changes. It is preferable that either or both of the pressure-sensitive adhesive layers 31 and 32 are composed of the pressure-sensitive adhesive layer of the present invention, but they do not necessarily have to be composed of the pressure-sensitive adhesive layer of the present invention.

[0214] The touch panel of the present invention is an image display device incorporating an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film.

[0215] FIG. 4 is a schematic diagram (cross-sectional view) showing a specific example of a preferred embodiment of the touch panel of the present invention. 4, 4 denotes a touch panel, 40, 41, and 42 denote adhesive layers, 43 denotes an image display panel, 44 denotes a touch sensor film, 45 denotes a polarizing film, 46 denotes a transparent substrate, and 47 denotes metal wiring. The metal wiring 47 is wired on one surface of the touch sensor film 44. The touch panel 4 is formed by laminating a polarizing film 45, an adhesive layer 42, an image display panel 43, an adhesive layer 41, a touch sensor film 44, an adhesive layer 40, and a transparent substrate 46 in this order, and the adhesive layer 40 is laminated on the surface of the touch sensor film 44 on which the metal wiring 47 is arranged.

[0216] At least one of the adhesive layers 40, 41, 42 is composed of the adhesive layer of the present invention. Since the touch panel 4 includes the adhesive layer of the present invention in its laminated structure, the touch panel 4 has high reliability in that the adhesive strength is unlikely to change due to environmental changes, and has excellent durability.

[0217] In the touch panel 4, the adhesive layer 40 is located on the most visible side of the laminated structure, and is most susceptible to the effects of the external environment, such as the outside temperature, humidity, and external light. In addition, since the adhesive layer 40 is laminated on the surface of the touch sensor film 44 on which the metal wiring 47 is arranged, it sufficiently conforms to the steps formed by the metal wiring 47, and no air bubbles remain. Therefore, the adhesive layer 40 is preferably made of the adhesive layer of the present invention, which is highly reliable and has excellent durability, and the adhesive strength of which is unlikely to change with environmental changes. Also, the adhesive layer 40 is preferably made of the adhesive layer of the present invention, which has excellent step conformability. It is preferable that either or both of the pressure-sensitive adhesive layers 41 and 42 are made of the pressure-sensitive adhesive layer of the present invention, but they do not necessarily have to be made of the pressure-sensitive adhesive layer of the present invention.

[0218] The method for forming the metal wiring on the touch sensor film is not particularly limited, but examples thereof include a method in which a pre-formed metal layer is removed by etching or the like, and a printing method.

[0219] The image display device and touch panel of the present invention may further include optical members such as a wavelength plate, a retardation film, and an optical compensation film. These optical members may be singular or plural. The manner of bonding these optical members is not particularly limited, but examples thereof include (1) a mode in which the optical member with the pressure-sensitive adhesive layer of the present invention is bonded to the optical member with the pressure-sensitive adhesive layer of the present invention via the pressure-sensitive adhesive sheet of the present invention, and (2) a mode in which the optical member with the pressure-sensitive adhesive layer of the present invention is bonded to the optical member with the pressure-sensitive adhesive layer of the present invention via a pressure-sensitive adhesive sheet other than the pressure-sensitive adhesive sheet of the present invention. EXAMPLES

[0220] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Note that the number of parts (parts by weight) indicates the number of parts of each component described.

[0221] [Production Example 1: Preparation of Prepolymer Composition A] A monomer mixture consisting of 56 parts by weight of 2-ethylhexyl acrylate (2EHA), 24 parts by weight of isostearyl acrylate (ISTA), 19 parts by weight of N-vinyl-2-pyrrolidone (NVP), and 1 part by weight of 4-hydroxybutyl acrylate (4-HBA) was mixed with 0.03 parts by weight of a photopolymerization initiator (product name "Omnirad184", manufactured by IGM Resins BV) and 0.03 parts by weight of a photopolymerization initiator (product name "Omnirad651", manufactured by IGM Resins BV), and the mixture was then irradiated with ultraviolet light until the viscosity (BH viscometer No. 5 rotor, 10 rpm, measurement temperature 30°C) reached approximately 20 Pa s, thereby obtaining a prepolymer composition A in which a portion of the monomer components had polymerized.

[0222] [Production Example 2: Preparation of Prepolymer Composition B] A monomer mixture consisting of 56 parts by weight of 2-ethylhexyl acrylate (2EHA), 24 parts by weight of isostearyl acrylate (ISTA), 14 parts by weight of N-vinyl-2-pyrrolidone (NVP), and 6 parts by weight of 4-hydroxybutyl acrylate (4-HBA) was mixed with 0.03 parts by weight of a photopolymerization initiator (product name "Omnirad184", manufactured by IGM Resins BV) and 0.03 parts by weight of a photopolymerization initiator (product name "Omnirad651", manufactured by IGM Resins BV), and the mixture was then irradiated with ultraviolet light until the viscosity (BH viscometer No. 5 rotor, 10 rpm, measurement temperature 30°C) reached approximately 20 Pa s, thereby obtaining a prepolymer composition B in which a portion of the monomer components had polymerized.

[0223] [Production Example 3: Preparation of Prepolymer Composition C] A monomer mixture consisting of 40.5 parts by weight of 2-ethylhexyl acrylate (2EHA), 40.5 parts by weight of isostearyl acrylate (ISTA), 18 parts by weight of N-vinyl-2-pyrrolidone (NVP), and 1 part by weight of 4-hydroxybutyl acrylate (4-HBA) was mixed with 0.05 parts by weight of a photopolymerization initiator (product name "Omnirad184", manufactured by IGM Resins BV) and 0.05 parts by weight of a photopolymerization initiator (product name "Omnirad651", manufactured by IGM Resins BV), and the mixture was then irradiated with ultraviolet light until the viscosity (BH viscometer No. 5 rotor, 10 rpm, measurement temperature 30°C) reached approximately 20 Pa s, thereby obtaining prepolymer composition C in which a portion of the monomer components were polymerized.

[0224] [Production Example 4: Preparation of Prepolymer Composition D] A monomer mixture consisting of 67 parts by weight of butyl acrylate (BA), 14 parts by weight of cyclohexyl acrylate (CHA), and 19 parts by weight of 4-hydroxybutyl acrylate (4-HBA) was mixed with 0.09 parts by weight of a photopolymerization initiator (product name "Omnirad184", manufactured by IGM Resins BV) and 0.09 parts by weight of a photopolymerization initiator (product name "Omnirad651", manufactured by IGM Resins BV), and the mixture was then irradiated with ultraviolet light until the viscosity (BH viscometer No. 5 rotor, 10 rpm, measurement temperature 30°C) reached approximately 20 Pa s, thereby obtaining a prepolymer composition D in which a portion of the monomer components had polymerized.

[0225] [Example 1] A mixture of 100 parts by weight of the prepolymer composition A obtained in Production Example 1, 1.5 parts by weight of hydrogenated 1,2-polybutadiene (trade name "BI-3000", number average molecular weight (Mn): 4750 (measured value), weight average molecular weight (Mw): 6150 (measured value), polydispersity (Mw / Mn): 1.30 (measured value), hydrogenation rate: 97% or more (catalog value), iodine value: 21 or less (catalog value), manufactured by Nippon Soda Co., Ltd.), and 1.5 parts by weight of hydrogenated 1,2-polybutadiene glycol (trade name "GI-2000", number average molecular weight (Mn ): 3110 (measured value), weight average molecular weight (Mw): 5090 (measured value), polydispersity (Mw / Mn): 1.64 (measured value), hydrogenation rate: 93% or more (catalog value), iodine value: 21 or less (catalog value), 21 parts by weight of Nippon Soda Co., Ltd. (manufactured by Nippon Soda Co., Ltd.), 0.07 parts by weight of trimethylolpropane triacrylate (TMPTA), and 0.3 parts by weight of a silane coupling agent (trade name "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd.) were added and mixed to obtain a pressure-sensitive adhesive composition (pre-cured composition).

[0226] The above adhesive composition was applied onto a polyethylene terephthalate (PET) release liner (heavy release liner, product name "MRF75", manufactured by Mitsubishi Plastics, Inc.) so that the final thickness (adhesive layer thickness) was 250 μm to form a coating layer (adhesive composition layer). Next, a PET release liner (light release liner, product name "MRE75", manufactured by Mitsubishi Plastics, Inc.) was provided on the above coating layer to cover the coating layer and block oxygen. Then, a laminate of MRF75 / coating layer (adhesive composition layer) / MRE75 was obtained. Next, a black light (Toshiba Corporation) was used to illuminate the top surface (MRF38 side) of the laminate at an illumination intensity of 5 mW / cm. 2 The laminate was irradiated with ultraviolet light for 300 seconds. The laminate was then dried in a dryer at 90°C for 2 minutes to volatilize the remaining monomers. As a result, a substrate-less double-sided PSA sheet was obtained, which was composed only of a PSA layer and had both sides protected by release liners.

[0227] [Examples 2 to 3, Comparative Example 1] A substrate-less double-sided pressure-sensitive adhesive sheet was obtained in the same manner as in Example 1, except that the formulation of the pressure-sensitive adhesive composition and the thickness of the pressure-sensitive adhesive layer were as shown in Table 1.

[0228] [Table 1]

[0229] Details of the components shown in Table 1 are as follows: (Prepolymer Composition) A: Prepolymer composition A produced in Production Example 1 B: Prepolymer composition B produced in Production Example 2 C: Prepolymer composition C produced in Production Example 3 D: Prepolymer composition D produced in Production Example 4

[0230] (monomer) HEA: 2-hydroxyethyl acrylate 4-HBA: 4-hydroxybutyl acrylate

[0231] (hydrogenated polyolefin) BI-3000: Product name "BI-3000", hydrogenated 1,2-polybutadiene, number average molecular weight (Mn): 4750 (measured value), weight average molecular weight (Mw): 6150 (measured value), polydispersity (Mw / Mn): 1.30 (measured value), hydrogenation rate: 97% or more (catalog value), iodine value: 21 or less (catalog value), manufactured by Nippon Soda Co., Ltd. GI-2000: Product name "GI-2000", hydrogenated 1,2-polybutadiene glycol, number average molecular weight (Mn): 3110 (measured value), weight average molecular weight (Mw): 5090 (measured value), polydispersity (Mw / Mn): 1.64 (measured value), hydrogenation rate: 97% or more (catalog value), iodine value: 21 or less (catalog value), manufactured by Nippon Soda Co., Ltd.

[0232] (Multifunctional acrylate) TMPTA: Trimethylolpropane triacrylate DPHA: Dipentaerythritol hexaacrylate

[0233] (Silane coupling agent) KBM-403: Product name "KBM-403", 3-glycidoxypropyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.

[0234] The actual values ​​of number average molecular weight (Mn), weight average molecular weight (Mw), and polydispersity (Mw / Mn) of the above hydrogenated polyolefins were measured by GPC (gel permeation chromatography) under the following conditions, and calculated based on polystyrene. Analytical equipment: GPC: HLC-8320GPC (Tosoh) Measurement conditions: Column: TSKgel SuperHZM-H / HZ4000 / HZ3000 / HZ2000 Column size: 6.0mm I.D. x 150mm Eluent: THF (tetrahydrofuran) Flow rate: 0.6mL / min Detector: Differential refractometer (RI) Column temperature: 40℃ Injection volume: 20μL The molecular weight was calculated in terms of polystyrene.

[0235] [Characteristics evaluation] The substrate-less double-sided PSA sheets of the Examples and Comparative Examples were subjected to the following measurements and evaluations.

[0236] (1) Method for measuring water absorption rate and water absorption rate The substrate-less double-sided PSA sheets of the Examples and Comparative Examples were cut into 1 cm squares, and the release liners on both sides were peeled off to give an adhesive layer, which was then set in a moisture adsorption / desorption measuring device (IGA-sorp, manufactured by Hiden) to measure moisture adsorption / desorption. The measurement mode was set to sequence mode, and the weight was measured over time while the environmental conditions were changed continuously in the program sequence shown in Table 2 below.

[0237] [Table 2]

[0238] The time when Program 2 was completed was considered to be in an absolutely dry state, and the weight change rates from the absolutely dry state to the time when Programs 2 to 6 were completed, calculated using the following formula, were taken as the water absorption rates X0, X25, X50, X75, and X90 (%), respectively. The results are shown in Table 3. Water absorption rate (%) = (weight at the end of each program - weight at the end of program 2 (absolutely dry state)) / (weight at the end of program 2 (absolutely dry state)) x 100

[0239] In addition, the time (min) required for the water absorption rate at the end of each program to reach half its value (water absorption rate at the end of the previous program) was measured from the water absorption rate at the start of Programs 3 to 6, and these were designated as water absorption rates T25, T50, T75, and T95, respectively. The results are shown in Table 3.

[0240] (2) Measurement method for adhesive strength The light release liners were peeled off from the substrate-less double-sided pressure-sensitive adhesive sheets of the Examples and Comparative Examples, and a PET film (Lumirror S10, manufactured by Toray Industries, Inc., thickness 25 μm) was attached to the exposed surface of the pressure-sensitive adhesive layer to obtain a laminate. Next, a test piece (20 mm wide × 150 mm long) was cut out from this laminate, the heavy release liner was peeled off, and the piece was attached to a glass plate (blue plate, green polished product, manufactured by Matsunami Glass Co., Ltd.) In this attachment, the test piece was pressed against the adherend by rolling a 2 kg roller back and forth once in an environment of 25°C. After the above-mentioned bonding, the specimen was allowed to stand at 23° C. for 2 minutes, and then a peel test was carried out in which the specimen was peeled from the glass plate, and the peel strength was measured as adhesive strength. In the above measurement, the measurement temperature was 23° C., the peel angle of the test piece relative to the adherend was 180°, the tensile speed of the test piece was 300 mm / min, and the peel length was 50 mm (measurement conditions for the peel test). After the pressure-sensitive adhesive layer was formed, the adhesive strength was measured within 12 hours by the above-mentioned method, and the initial adhesive strength (N / 20 mm) was defined as Y0. The test pieces were then stored under conditions of 23°C and 50% RH for 24 hours, 48 ​​hours, 120 hours, 144 hours, 168 hours, and 216 hours, and the adhesive strength (N / 20 mm) was measured using the method described above. The results were Y24, Y48, Y120, Y144, Y168, and Y216, respectively. A graph showing the change in adhesive strength over time is shown in FIG. 5, and the initial adhesive strength Y0, the adhesive strength after 48 hours of storage Y48, and the rate of change in adhesive strength from Y0 to Y48 ((Y0-Y48) / Y0x100) (%) are shown in Table 3. In Comparative Example 1, where X90 exceeds 1.5%, a rapid decrease in adhesive strength was observed 48 hours after the initial adhesive strength, whereas in Examples 1 to 3, where X90 is 1.5% or less, there was little change in adhesive strength from the initial adhesive strength, demonstrating highly reliable adhesive strength.

[0241] [Table 3]

[0242] Variations of the present invention are listed below. [Appendix 1] A pressure-sensitive adhesive composition for forming a pressure-sensitive adhesive layer used for attaching an optical member of an image display device, comprising: The pressure-sensitive adhesive composition satisfies the following formula (1), where X90(%) is the water absorption rate when the pressure-sensitive adhesive layer is stored for 360 minutes under conditions of 23° C. and 90% RH: X90≦1.5% (1) [Appendix 2] The pressure-sensitive adhesive composition according to claim 1, wherein the water absorption rate of the pressure-sensitive adhesive layer when stored for 240 minutes under conditions of 23°C and 25% RH is defined as X25 (%), which satisfies the following formula (2): X90-X25≦1.5% (2) [Appendix 3] The pressure-sensitive adhesive composition according to claim 1 or 2, wherein T90 (min) is a time required for the pressure-sensitive adhesive layer to reach half of the water absorption rate X90 (%) when stored for 360 minutes under conditions of 23°C and 75% RH from the water absorption rate X75 (%) when stored for 360 minutes under conditions of 23°C and 90% RH, satisfies the following formula (3): T90≧16 minutes (3) [Appendix 4] The pressure-sensitive adhesive composition according to Appendix 3, which satisfies the following formula (4), when the time required for the pressure-sensitive adhesive layer to reach half of the water absorption rate X25 (%) when stored for 240 minutes under conditions of 23°C and 25% RH from an absolutely dry state is defined as T25 (min). T90 / T25≧1.0 (4) [Appendix 5] An adhesive layer formed from the adhesive composition according to any one of claims 1 to 4. [Appendix 6] An adhesive sheet having the adhesive layer according to claim 5. [Appendix 7] An optical member with a pressure-sensitive adhesive layer, comprising the pressure-sensitive adhesive sheet according to claim 6 attached to at least one surface of the optical member. [Appendix 8] An image display device comprising the pressure-sensitive adhesive layer-attached optical member according to claim 7. [Appendix 9] 9. The image display device according to claim 8, which is a touch panel. [Explanation of symbols]

[0243] 1 Adhesive sheet 10 Adhesive layer 11, 12 Release liner 2A Optical components with adhesive layer 2B Touch sensor film with adhesive layer 20 Adhesive layer 21 Optical components 22 Release Liner 23 Touch sensor film 24 Metal wiring 3 Image display device 30, 31, 32 Adhesive layer 33 Image display panel 34, 35 Polarizing film 36 Transparent Substrate 4. Touch Panel 40, 41, 42 Adhesive layer 43 Image display panel 44 Touch sensor film 45 Polarizing Film 46 Transparent Substrate 47 Metal wiring

Claims

1. A pressure-sensitive adhesive composition for forming a pressure-sensitive adhesive layer used for attaching an optical member of an image display device, comprising: A pressure-sensitive adhesive composition, wherein when the pressure-sensitive adhesive layer is stored for 360 minutes under conditions of 23° C. and 90% RH, the water absorption rate is defined as X90 (%), and the composition satisfies the following formula (1): X90≦1.5% … (1)

2. The pressure-sensitive adhesive composition according to claim 1 , wherein the pressure-sensitive adhesive layer has a water absorption rate X25 (%) when stored for 240 minutes under conditions of 23° C. and 25% RH, and the composition satisfies the following formula (2): X90-X25≦1.5%... (2)

3. 2. The pressure-sensitive adhesive composition according to claim 1, wherein the pressure-sensitive adhesive layer has a water absorption rate X75(%) when stored for 360 minutes under conditions of 23° C. and 75% RH, and the water absorption rate X90(%) when stored for 360 minutes under conditions of 23° C. and 90% RH is defined as a time T90 (min), which satisfies the following formula (3): T90≧16 minutes... (3)

4. 3. The pressure-sensitive adhesive composition according to claim 2, wherein the pressure-sensitive adhesive layer has a water absorption rate X75(%) when stored for 360 minutes under conditions of 23° C. and 75% RH, and the water absorption rate X90(%) when stored for 360 minutes under conditions of 23° C. and 90% RH is defined as a time T90 (min), which satisfies the following formula (3): T90≧16 minutes... (3)

5. 4. The pressure-sensitive adhesive composition according to claim 3, wherein the pressure-sensitive adhesive layer is stored from an absolutely dry state under conditions of 23°C and 25% RH for 240 minutes, and the time required for the water absorption rate to reach half of the water absorption rate X25 (%) is defined as T25 (min), which satisfies the following formula (4): T90 / T25≧1.0... (4)

6. The pressure-sensitive adhesive composition according to claim 4, wherein the pressure-sensitive adhesive layer is stored from an absolutely dry state under conditions of 23°C and 25% RH for 240 minutes, and the time required for the water absorption rate to reach half of the water absorption rate X25 (%) is defined as T25 (min), which satisfies the following formula (4): T90 / T25≧1.0... (4)

7. A pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition according to any one of claims 1 to 6.

8. A pressure-sensitive adhesive sheet having the pressure-sensitive adhesive layer according to claim 7.

9. An optical member with a pressure-sensitive adhesive layer, comprising the pressure-sensitive adhesive sheet according to claim 8 attached to at least one surface of the optical member.

10. An image display device comprising the pressure-sensitive adhesive layer-attached optical member according to claim 9.

11. The image display device according to claim 10, which is a touch panel.

Citation Information

Patent Citations

  • Adhesive double coated sheet and method of affixing touch panel to display device

    JP2003238915A

  • Double-sided adhesive sheet and display device with touch panel

    JP2003342542A

  • Pressure sensitive adhesive double-sided sheet and display device with touch panel

    JP2004231723A